Electroactive materials for metal-ion batteries

By depositing electroactive materials and modified materials in the pores of the porous particle framework in multiple steps to form composite particulate materials, the problem of capacity loss of anode materials in the prior art during multiple cycles is solved, and higher electrochemical performance and cycle stability are achieved.

CN118120076BActive Publication Date: 2025-04-29NEXEON LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280070265.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-21
Filing Date
2022-10-21
Publication Date
2025-04-29
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The anode materials of existing rechargeable metal ion batteries are difficult to maintain sufficient capacity and structural stability during multiple charge/discharge cycles, resulting in loss of electrochemical capacity.

Method used

Using a multi-step deposition process, a composite particulate material is formed by depositing multiple electroactive material domains and modified material domains in the pores of the porous particle backbone, limiting the length and size of the electroactive material and reducing surface exposure.

Benefits of technology

The reversible capacity retention rate of the battery is improved, the formation of solid electrolyte interface layer is reduced, the cycle life of the battery is extended, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention relates to a granular material and a method for preparing the same. The granular material is composed of a plurality of composite particles. The composite particles include a porous particle skeleton, wherein the porous particle skeleton contains micropores and / or mesopores. The total pore volume of the micropores and mesopores measured by gas adsorption is between 0.4 and 2.2 cm 3 The composite particles include a plurality of electroactive material domains and a plurality of modifying material domains disposed within the internal pore volume of the porous particle framework. At least a portion of the modifying material domains are located between adjacent electroactive material domains.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates generally to electroactive materials suitable for use in electrodes of rechargeable metal ion batteries, and more particularly to particulate materials having high electrochemical capacity suitable for use as anode active materials in rechargeable metal ion batteries. Background Art

[0002] Rechargeable metal ion batteries are widely used in portable electronic devices, such as mobile phones and laptops, and are increasingly used in electric vehicles or hybrid vehicles. Rechargeable metal ion batteries generally include an anode in the form of a metal current collector having a layer of electroactive material, which is defined herein as a material that can embed and release metal ions during charging and discharging of the battery. The terms "cathode" and "anode" are used herein in the following sense: the battery is connected to a load so that the anode is the negative electrode. When the metal ion battery is charged, the metal ions are transported from the cathode layer containing the metal ions to the anode via the electrolyte and are embedded in the anode material. The term "battery" herein refers to both devices containing a single anode and a single cathode and devices containing multiple anodes and / or multiple cathodes.

[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal ion batteries. To date, commercial lithium ion batteries have been largely limited by the use of graphite as the anode active material. When the graphite anode is charged, lithium is intercalated between the graphite layers to form a lithium ion battery with the empirical formula Li x C6 (where x is greater than 0 and less than or equal to 1). Thus, the maximum theoretical capacity of graphite in lithium-ion batteries is 372 mAh / g, with actual capacities slightly lower (approximately 340 to 360 mAh / g). Other materials such as silicon, tin, and germanium can intercalate lithium at significantly higher capacities than graphite, but have not been widely used commercially due to difficulties in maintaining sufficient capacity over multiple charge / discharge cycles.

[0004] In particular, silicon is considered a promising graphite substitute for making rechargeable metal ion batteries with high weight and volumetric capacity due to its very high lithium capacity (see, for example, Insertion Electrode Materials for rechargeable Lithium Batteries, Winter, M et al., Adv. Mater. 1998, 10, No. 10). At room temperature, the theoretical maximum specific capacity of silicon in lithium ion batteries is about 3,600 mAh / g (based on Li 15Si4 is calculated). However, when silicon is lithiated to its maximum capacity, lithium is embedded in bulk silicon, resulting in a substantial increase in the volume of the silicon material, up to 400% of its original volume. Repeated charge-discharge cycles cause significant mechanical stress in the silicon material, leading to the breakage and delamination of the silicon anode material. The volume shrinkage of silicon particles during delithiation may result in loss of electrical contact between the anode material and the current collector. Another difficulty is that the solid electrolyte interface (SEI) layer formed on the silicon surface does not have sufficient mechanical tolerance to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface leads to further electrolyte decomposition and increased SEI layer thickness as well as irreversible lithium consumption. These damage mechanisms together lead to unacceptable electrochemical capacity loss during continuous charge and discharge cycles.

[0005] Various approaches have been proposed to overcome the problems associated with the volume changes observed when silicon-containing anodes are charged. Fine silicon structures such as silicon films and silicon nanoparticles with cross-sections below about 150 nm have been reported to be more tolerant of volume changes during charge and discharge than silicon particles in the micrometer size range. However, none of them are suitable for commercial-scale applications in their unmodified form; nanometer-sized particles are difficult to prepare and handle, and silicon films do not provide sufficient bulk capacity.

[0006] WO 2007 / 083155 discloses that improved capacity retention can be obtained using silicon particles with a high aspect ratio (i.e., the ratio of the largest dimension to the smallest dimension of the particle). The small cross-section of such particles reduces the structural stress on the material due to volume changes during charge and discharge. However, such particles can be difficult and expensive to manufacture and can be fragile. In addition, the high surface area can lead to excessive SEI formation, resulting in excessive capacity loss during the first charge-discharge cycle.

[0007] It is also generally known that electroactive materials such as silicon can be deposited in the pores of porous support materials such as activated carbon materials. These composite materials provide some of the beneficial charge-discharge properties of nanosized silicon particles while avoiding the handling difficulties of nanoparticles. Guo et al. (Journal of Materials Chemistry A, 2013, pp. 14075-14079) disclose a silicon-carbon composite material in which a porous carbon substrate provides a conductive skeleton and silicon nanoparticles are deposited in a uniformly distributed pore structure of the substrate. The known composite material has an improved capacity retention rate over multiple charging cycles, but the initial capacity of the composite material (in mAh / g) is significantly lower than the initial capacity of the silicon nanoparticles.

[0008] The inventors have previously reported the development of a class of electroactive materials with composite structures, in which nanometer-sized electroactive materials (such as silicon) are deposited into a pore network of highly porous conductive granular materials (such as porous carbon materials). For example, WO 2020 / 095067 and WO 2020 / 128495 report that the improved electrochemical performance of these materials can be attributed to the way in which the electroactive materials are located in porous materials in the form of small domains with a size of less than a few nanometers. These fine electroactive structures are believed to have lower resistance to elastic deformation and higher fracture resistance than larger electroactive structures, and are therefore capable of lithiation and delithiation without excessive structural stress. As a result, the electroactive material exhibits good reversible capacity retention with multiple charge and discharge cycles. Secondly, by controlling the loading amount of silicon in the porous carbon skeleton, only a portion of the pore volume is occupied by silicon in the uncharged state, and the unoccupied pore volume of the porous carbon skeleton can accommodate a significant amount of silicon expansion internally. Furthermore, by locating nano-sized electroactive material domains within small mesopores and / or micropores as described above, only small regions of the electroactive material surface are accessible to the electrolyte, thereby limiting SEI formation. Additional exposure during subsequent charge-discharge cycles is largely prevented, resulting in a significant reduction in the role of SEI formation as a failure mechanism leading to capacity loss. This is in stark contrast to the excessive SEI formation that is a feature of materials disclosed by, for example, Guo (see above).

[0009] The materials described in WO2020 / 095067 and WO 2020 / 128495 have been synthesized in different reactor systems (stationary, rotary and FBR) by chemical vapor infiltration (CVI). At atmospheric pressure and at a temperature of 400 to 700 ° C, the porous conductive particles are contacted with a silicon-containing precursor flow (CVI) (typically silane gas) until the desired amount of silicon is deposited into micropores and small mesopores. The deposition of silicon is carried out in a single step (single-step deposition). Although it is convenient to deposit silicon in a single step, this provides little control over the length size of the deposited silicon. It is believed that the deposition of coarser silicon domains results in a reduction in the reversible capacity retention rate due to excessive structural stress and uncontrolled SEI formation during subsequent charge-discharge cycles. Summary of the invention

[0010] There is therefore a need in the art for composite particles containing electroactive materials that overcome the shortcomings of composite particles obtained by existing single-step and multi-step deposition processes.

[0011] In a first aspect, the present invention provides a granular material consisting of a plurality of composite particles, wherein the composite particles comprise:

[0012] (a) a porous particle framework comprising micropores and / or mesopores, wherein the total pore volume of the micropores and mesopores measured by gas adsorption is between 0.4 and 2.2 cm 3 / g range;

[0013] (b) a plurality of electroactive material domains and a plurality of modifying material domains disposed within the interior pore volume of the porous particle framework, wherein at least a portion of the modifying material domains are located between adjacent electroactive material domains.

[0014] Therefore, the present invention generally relates to a composite particle material, the composite particle material includes a plurality of electroactive material (e.g., silicon) domains within the pore network of porous particles. Therefore, porous particles form a skeleton for electroactive material domains. As used herein, the term "electroactive material domain" refers to an electroactive material body with a maximum size, such as elemental silicon, and the maximum size is determined by the size of the micropores and / or mesopores of the porous particles in which they are located. Therefore, the electroactive domain can be described as a nano-sized electroactive domain, wherein the term "nano-size" is understood to generally refer to a size less than 100nm. However, due to the size of the micropores and mesopores, the maximum size of the electroactive material domain in any direction is typically less than 50nm, and is generally significantly less than 50nm. The domain, for example, can take the form of a bounded layer or region of a regular or irregular particle or coating. The electroactive material domain is present in combination with a modified material domain, wherein at least a portion of the modified material domain is located between adjacent electroactive material domains. Multiple electroactive material domains can be discrete electroactive material domains. The electroactive material domain may comprise (or consist of) an amorphous electroactive material or a crystalline electroactive material.

[0015] When compared with materials including similar porous particle skeletons but in which there is no modifying material, a variety of different factors contribute to the improved performance of these materials. The modifying material can act as a barrier that effectively prevents the domain of the discrete electroactive material from increasing in size as more electroactive materials are deposited in the porous particles (e.g., in another deposition step). Therefore, the modifying material limits the length dimension of the deposited electroactive material, making it possible to further deposit the electroactive material to form a discrete electroactive material domain. Therefore, a composite particle having a desired electroactive material loading and a desired length dimension of the electroactive material domain is obtained. In addition, the modifying material can reduce the exposed surface area of ​​the electroactive material domain, thereby minimizing SEI formation and oxidation on the surface of the electroactive material. In addition, the modifying material effectively prevents the electroactive material from being exposed to the electrolyte, thereby reducing SEI formation. During the long-term circulation of the composite material, the structure of the composite particle may be destroyed, opening voids and channels, thereby causing exposure of the electroactive surface previously located in the closed pore space. If the composite material is circulated at a higher temperature, when the reaction energy is increased, due to repeated volume changes and chemical interactions with the electrolyte solvent and other battery components, this problem will be aggravated. Adding a modifying material protects the surface of the electroactive material domain, thus reducing the amount of degradation that may occur in this case. The modifying material can also be used as a conductive component, for example, a conductive carbon layer (such as a hydrocarbon passivation layer or a nitride passivation layer) can be used as a modifying material, which serves as a conductivity enhancer located in the entire internal volume of the composite particle. This is considered to further improve the cycle efficiency and improve the rate performance of the composite.

[0016] The porous particle skeleton comprises a three-dimensional interconnected open pore network including micropores and / or mesopores and optionally small volumes of macropores. According to conventional IUPAC terminology, the term "micropore" is used herein to refer to pores with a diameter less than 2 nm, the term "mesopore" is used herein to refer to pores with a diameter of 2-50 nm, and the term "macroporous" is used to refer to pores with a diameter greater than 50 nm.

[0017] References herein to the volume of micropores, mesopores and macropores in the porous particle skeleton and any reference to the distribution of pore volume within the porous particle skeleton should be understood to refer to the internal pore volume of the porous particle skeleton itself (i.e., in the form of porous particles before deposition of electroactive materials and modifying materials). References herein to the BET surface area of ​​the porous particle skeleton should also be understood to refer to the BET surface area of ​​the porous particle skeleton itself.

[0018] The porous particle framework is characterized by a porous 3 / g range of micropores and mesopores (i.e., the total pore volume in the range of 0 to 50 nm). Typically, the porous particle skeleton includes both micropores and mesopores. However, it is not excluded that a porous particle skeleton can be used that includes micropores but not mesopores or includes mesopores but not micropores.

[0019] More preferably, the total volume of the micropores and mesopores in the porous particle skeleton is at least 0.45 cm 3 / g, or at least 0.5cm 3 / g, or at least 0.55cm 3 / g, or at least 0.6cm 3 / g, or at least 0.65cm 3 / g, or at least 0.7cm 3 / g, or at least 0.75cm 3 / g, or at least 0.8cm 3 / g, or at least 0.85cm 3 / g, or at least 0.9cm 3 / g, or at least 0.95cm 3 / g, or at least 1cm 3 The use of a high porosity framework can be advantageous because it enables a larger amount of silicon to be accommodated within the pore structure.

[0020] The internal pore volume of the porous particle skeleton is suitably limited to a value at which the increased fragility of the porous particle skeleton outweighs the advantages of the increased pore volume to accommodate a greater amount of silicon. Preferably, the total volume of micropores and mesopores in the porous particle skeleton does not exceed 2 cm 3 / g, or not more than 1.8cm 3 / g, or not more than 1.6cm 3 / g, or not more than 1.5cm 3 / g, or not more than 1.45cm 3 / g, or not more than 1.4cm 3 / g, or not more than 1.35cm 3 / g, or not more than 1.3cm 3 / g, or not more than 1.25cm 3 / g, or not more than 1.2cm 3 / g, or not more than 1.1, or not more than 1, or not more than 0.95.

[0021] Preferably, the total volume of micropores and mesopores in the porous particle skeleton is between 0.45 and 2.2 cm 3 / g, or 0.5 to 2cm 3 / g, or 0.55 to 2cm 3 / g, or 0.6 to 1.8 cm 3 / g, or 0.65 to 1.8 cm 3 / g, or 0.7 to 1.6 cm 3 / g, or 0.7 to 1.5 cm 3 / g, or 0.7 to 1.4 cm 3 / g range.

[0022] The total volume of micropores and mesopores in the porous particle skeleton can also be between 0.55 and 1.4 cm 3 / g, or 0.6 to 1.4 cm 3 / g, or 0.6 to 1.3 cm 3 / g, or 0.65 to 1.3 cm 3 / g, or 0.65 to 1.2 cm 3 / g, or 0.7 to 1.2 cm 3 / g, or 0.7 to 1.1 cm 3 / g, or 0.7 to 1cm 3 / g, or 0.75 to 0.95 cm 3 / g range.

[0023] The total volume of micropores and mesopores in the porous particle skeleton can also be between 0.4 and 0.75 cm 3 / g, or 0.4 to 0.7 cm 3 / g, or 0.4 to 0.65cm 3 / g, 0.45 to 0.75 cm 3 / g, or 0.45 to 0.7 cm 3 / g, or 0.45 to 0.65cm 3 / g, or 0.45 to 0.6 cm 3 / g range.

[0024] The total volume of micropores and mesopores in the porous particle skeleton can also be between 0.6 and 2 cm 3 / g, or 0.6 to 1.8 cm 3 / g, or 0.7 to 1.8 cm 3 / g, or 0.7 to 1.6 cm 3 / g, or 0.8 to 1.6 cm 3 / g, or 0.8 to 1.5 cm 3 / g, or 0.8 to 1.4 cm 3 / g, or 0.9 to 1.5cm 3 / g, or 0.9 to 1.4 cm 3 / g, or 1 to 1.4cm 3 / g range.

[0025] The general term "PD nThe term "pore size" as used herein refers to the volume nth percentile pore size based on the total volume of micropores and mesopores. For example, as used herein, the term "PD 50 The term "pore size" refers to the pore size below which 50% of the total micropore and mesopore volume is measured.

[0026] PD of porous particle skeleton 50 The pore size may be no more than 30 nm, and preferably no more than 25 nm, or no more than 20 nm, or no more than 15 nm, or no more than 12 nm, or no more than 10 nm, or no more than 8 nm, or no more than 6 nm, or no more than 5 nm, or no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm, or no more than 1.5 nm. As used herein, the term "PD 50 By "pore size" is meant the volume median pore size based on the total volume of micropores and mesopores. Thus, at least 50% of the total volume of micropores and mesopores is preferably in the form of pores having a diameter of less than 30 nm.

[0027] PD of porous particle skeleton 30 The pore size may be no more than 25 nm, or no more than 20 nm, or no more than 15 nm, or no more than 12 nm, or no more than 10 nm, or no more than 8 nm, or no more than 6 nm, or no more than 5 nm, or no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm, or no more than 1 nm.

[0028] PD of porous particle skeleton 90 The pore size may be no more than 35 nm, or no more than 30 nm, or no more than 25 nm, or no more than 20 nm, or no more than 15 nm, or no more than 12 nm, or no more than 10 nm, or no more than 8 nm, or no more than 6 nm, or no more than 5 nm, or no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm. Preferably, the PD of the porous particle skeleton is 90 The pore size is at least 2.5 nm, or at least 3 nm, or at least 3.5 nm, or at least 4 nm. For example, the PD of the porous particle skeleton 90 The pore size is preferably in the range of 2.5 to 20 nm, or 3 to 15 nm, or 3.5 to 10 nm, or 4 to 8 nm.

[0029] PD of porous particle skeleton 10 The pore size may be no more than 10 nm, or no more than 9 nm, or no more than 8 nm, or no more than 7 nm, or no more than 6 nm, or no more than 5 nm, or no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm, or no more than 1.5 nm, or no more than 1 nm. Preferably, the PD of the porous particle skeleton is 10The pore size is at least 0.3 nm, or at least 0.4 nm, or at least 0.5 nm. For example, the PD of the porous particle skeleton 10 The pore size is preferably in the range of 0.3 to 10 nm, or 0.3 to 5 nm, or 0.3 to 1 nm, or 0.4 to 1 nm, or 0.5 to 1 nm.

[0030] For the avoidance of doubt, in order to determine the PD n value, without taking into account any macropore volume (pores larger than 50 nm).

[0031] Preferably, the volume of the pores in the porous particle framework is at least 0.25 cm 3 / g, or at least 0.3cm 3 / g, at least 0.4cm 3 / g, or at least 0.5cm 3 Preferably, the volume of the micropores in the porous particle skeleton does not exceed 1.7 cm 3 / g, or not more than 1.5cm 3 / g, or not more than 1.2cm 3 / g. The volume of the micropores in the porous particle skeleton can be between 0.3 and 1.7 cm 3 / g, or 0.3 to 1.5 cm 3 / g, or 0.3 to 1.2 cm 3 The volume of the micropores in the porous particle skeleton can be between 0.4 and 1.7 cm 3 / g, or 0.5 to 1.7 cm 3 The volume of the micropores in the porous particle skeleton can be between 0.4 and 1.5 cm 3 / g, or 0.5 to 1.2 cm 3 A certain amount of micropore-sized voids in the porous particle framework is conducive to the deposition of small-sized electroactive material domains in the pores, while if the micropore volume is too high, it may excessively restrict the penetration of the electroactive domains and the precursors of the modified domains into the porous particle framework.

[0032] The volume ratio of micropores to mesopores in the porous particle skeleton may be substantially in the range of 100:0 to 0: 100. Preferably, the volume ratio of micropores to mesopores is 90:10 to 30:70, or 85:15 to 40:60, or 80:20 to 50:50, or 70:30 to 55:45.

[0033] The quenched solid density functional theory (QSDFT) was used according to the standard method described in ISO 15901-2 and ISO 15901-3, using nitrogen adsorption at 77 K down to 10 -6The relative pressure p / p0 of pore volume is used to determine the total volume of micropores and mesopores and the pore size distribution of micropores and mesopores. Nitrogen adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure increases, the gas first condenses in the pores with the smallest diameter, and the pressure increases until a saturation point is reached, at which all pores are filled with liquid. The nitrogen pressure is then gradually reduced to evaporate the liquid from the system. Analysis of the adsorption and desorption isotherms and the hysteresis between them enables the determination of the pore volume and pore size distribution. Suitable instruments for measuring pore volume and pore size distribution by nitrogen adsorption include TriStar II and TriStar IIPlus porosity analyzers (which are available from Micromeritics Instrument Corporation in the United States), and Autosorb IQ porosity analyzer (which is available from Quantachrome Instruments).

[0034] Nitrogen adsorption is effective for measuring pore volume and pore size distribution for pores up to 50 nm in diameter, but is less reliable for pores with much larger diameters. For the purposes of the present invention, therefore, pore volume and pore size distribution are determined using nitrogen adsorption only for pores up to and including 50 nm in diameter (i.e., only for micropores and mesopores). 50 The values ​​are likewise determined only relative to the total volume of micropores and mesopores.

[0035] Given the limitations of available analytical techniques, it is not possible to measure pore volume and pore size distribution over the entire range of micropores, mesopores and macropores using a single technique. Where the porous particle or porous particle framework includes macropores, the volume of pores with diameters in the range of greater than 50 nm to 100 nm can be measured by mercury intrusion porosimetry, and preferably not more than 0.3 cm 3 / g, or not more than 0.2cm 3 / g, or not more than 0.1cm 3 / g, or not more than 0.05cm 3 Although a small fraction of macropores may be useful in facilitating the entry of electrolyte into the pore network, the advantages of the present invention are substantially obtained by accommodating silicon in micropores and smaller mesopores.

[0036] Any pore volume measured by mercury porosimetry for pore sizes below 50 nm is not considered (as described above, nitrogen adsorption is used to characterize mesopores and micropores). For the purposes of this invention, pore volume measured by mercury porosimetry above 100 nm is assumed to be interparticle porosity and is also not considered.

[0037] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying varying levels of pressure to a sample of the material immersed in mercury. The pressure required to cause mercury to penetrate into the pores of the sample is inversely proportional to the size of the pores. The values ​​obtained by mercury intrusion porosimetry reported herein are obtained according to ASTM UOP578-11, where for mercury at room temperature, the surface tension γ is 480 mN / m and the contact angle is 140 o The density of mercury at room temperature is 13.5462 g / cm 3 A variety of high precision mercury porosimetry instruments are commercially available, such as the AutoPore IV series of automated mercury porosimeter, available from Micromeritics Instrument Corporation in the United States. For a complete overview of mercury porosimetry, reference may be made to PA Webb and C. Orr, "Analytical Methods in Fine Particle Technology", 1997, Micromeritics Instrument Corporation, ISBN 0-9656783-0.

[0038] It should be understood that intrusion techniques such as gas adsorption and mercury intrusion are only valid for determining the pore volume of pores accessible to nitrogen or mercury from outside the porous particle. The porosity values ​​specified herein should be understood to refer to the volume of open pores (i.e., pores accessible to fluid from outside the porous particle). In this context, completely enclosed pores that cannot be identified by nitrogen adsorption or mercury intrusion should not be considered when determining porosity values. Likewise, any pore volume located in pores so small as to be below the detection limit of nitrogen adsorption is also not considered.

[0039] The pore size distribution of the porous particle skeleton can be unimodal, bimodal or multimodal. As used herein, the term "pore size distribution" relates to the distribution of pore sizes of the porous particle skeleton relative to the cumulative total internal pore volume. Bimodal or multimodal pore size distributions may be preferred because the close proximity between micropores and pores with larger diameters provides the advantage of efficient ion transport from the porous network to the silicon.

[0040] The BET surface area of ​​the porous particle skeleton is preferably at least 100 m 2 / g, or at least 500m 2 / g, or at least 750m 2 / g, or at least 1,000m 2 / g, or at least 1,250m 2 / g, or at least 1,500m 2 / g. As used herein, the term "BET surface area" should be taken to mean the surface area per unit mass calculated from the measurement of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller principle according to ISO 9277. Preferably, the BET surface area of ​​the porous particle skeleton does not exceed 4,000 m 2 / g, or not more than 3,500m 2 / g, or not more than 3,250m 2 / g, or not more than 3,000m 2 / g, or not more than 2,500m 2 / g, or not more than 2,000m 2 / g. For example, the BET surface area of ​​the porous particle skeleton can be 100m 2 / g to 4,000m 2 / g, or 500m 2 / g to 4,000m 2 / g, or 750m 2 / g to 3,500m 2 / g, or 1,000m 2 / g to 3,250m 2 / g、1,000m 2 / g to 3,000m 2 / g, or 1,000m 2 / g to 2,500m 2 / g, or 1,000m 2 / g to 2,000m 2 / g range.

[0041] The porous particle skeleton is preferably conductive. The conductive porous particle skeleton comprises or consists of a conductive carbon material. The conductive porous carbon particle skeleton preferably comprises at least 80% by weight of carbon, more preferably at least 90% by weight of carbon, more preferably at least 95% by weight of carbon, and optionally at least 98% by weight or at least 99% by weight of carbon. The carbon may be crystalline carbon or amorphous carbon, or a mixture of amorphous carbon and crystalline carbon. The carbon may be carbon or soft carbon.

[0042] As used herein, the term "hard carbon" refers to a disordered carbon matrix in which the carbon atoms are found primarily as sp 2 Hybrid state (triple bond). The polyaromatic domains are cross-linked using chemical bonds such as C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbon cannot be converted into graphite at high temperatures. Hard carbon has graphite-like properties, which is reflected by the large G band (~1600 cm) in the Raman spectrum. -1However, the carbon is not completely graphitic, as evidenced by the distinct D band (~1350 cm -1 )prove.

[0043] As used herein, the term "soft carbon" also refers to a disordered carbon matrix in which the carbon atoms are found primarily in sp 2 The hybridization state (triple bonds) is in polyaromatic domains with sizes ranging from 5 to 200 nm. In contrast to hard carbon, the polyaromatic domains in soft carbon are associated by intermolecular forces rather than cross-linked by chemical bonds. This means that they will graphitize at high temperatures. The porous carbon skeleton preferably contains at least 50% sp 2 Hybridized carbon (measured by XPS). For example, the porous carbon framework may suitably contain 50% to 98% sp 2 Hybridized carbon, 55% to 95% sp 2 Hybridized carbon, 60% to 90% sp 2 Hybridized carbon, or 70% to 85% sp 2 Hybridized carbon.

[0044] A variety of different materials can be used to prepare porous particles suitable for forming a porous particle skeleton by pyrolysis. Examples of usable organic materials include: plant biomass, which includes lignocellulosic materials (such as coconut shells, rice husks, wood, etc.), and fossil carbon sources, such as coal. Examples of resins and polymer materials that form porous carbon particles during pyrolysis include: phenolic resins, novolac resins, asphalt, melamine materials, polyacrylate materials, polystyrene materials, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and various copolymers of monomer units comprising acrylic ester monomers, styrene monomers, α-olefins, vinyl pyrrolidone and other ethylenically unsaturated monomers. Various carbon materials can be obtained in the art according to the raw materials and conditions of the pyrolysis process. Porous carbon particles of various specifications can be obtained from commercial suppliers.

[0045] The porous carbon particles may be subjected to a chemical or gas activation process to increase the volume of the mesopores and micropores. Suitable activation processes include contacting the pyrolytic carbon with one or more selected from oxygen, water vapor, CO, CO2 and KOH at a temperature in the range of 600 to 1000°C.

[0046] Mesopores can also be obtained by known templating processes using removable pore formers such as MgO and other colloidal or polymer templates that can be removed by thermal or chemical means after pyrolysis or activation.

[0047] Alternatives to carbon-based particle frameworks include porous particle frameworks comprising titanium nitride (TiN), titanium carbide (TiC), silicon carbide (SiC), nickel oxide (NiOx), titanium silicon nitride (TiSiN), nickel nitride (Ni3N), molybdenum nitride (MoN), titanium oxynitride (TiO x N 1-x ), silicon oxycarbide (SiOC), boron nitride (BN) or vanadium nitride (VN). Preferably, the porous particle framework comprises titanium nitride (TiN), silicon oxycarbide (SiOC) or boron nitride (BN). Additional alternatives to the carbon-based particle framework include porous particle frameworks comprising: metal oxides, such as having the formula TiO x An oxide of titanium, wherein the value of x is greater than 1 and less than 2.

[0048] The shape of the porous particle skeleton can be irregular or spherical.

[0049] Multiple electroactive material domains can respectively contain the same electroactive material, or different electroactive material domains can contain different electroactive materials. Preferably, the electroactive material domain comprises an electroactive material selected from the following: element silicon, element tin, element germanium, element aluminum and mixtures and alloys thereof. For example, some electroactive material domains can contain element silicon (or be composed of element silicon), while other electroactive material domains can contain element germanium (or be composed of element germanium). The preferred electroactive material is silicon. Preferably, at least a portion of the electroactive material domains contains element silicon or is composed of element silicon. More preferably, all electroactive material domains contain element silicon or are composed of element silicon.

[0050] As used herein, a "modifying material domain" refers to a domain of material having a different chemical composition than an electroactive material domain. At least a portion of a modifying material domain is located between adjacent electroactive material domains. The requirement that "at least a portion of a modifying material domain is located between adjacent electroactive material domains" should be interpreted to mean that the pore space of the porous particle framework is occupied, in sequence, by an electroactive material domain, then a modifying material domain, and then an electroactive material domain. Thus, the electroactive material does not form an extended network throughout the pore space, but is interrupted by the modifying material domains. Thus, within a single pore space there are components of the material domains in the following order:

[0051] [One or more electroactive material domains]

[0052] ↓

[0053] [One or more modified material domains]

[0054] ↓

[0055] [One or more electroactive material domains]

[0056] As discussed in more detail below, this material sequence is typically obtained by sequentially depositing electroactive materials and modifying materials into the pores of a porous particle backbone. This sequence can be appropriately extended by additional electroactive material domains and / or by additional modifying material domains.

[0057] The modifying material domains located between adjacent electroactive material domains can act as a barrier separating the electroactive material domains, thereby restricting the length scale of the continuous electroactive material domains within the composite particles. The modifying material domains located between adjacent electroactive material domains can act as a barrier separating the electroactive material domains. The modifying material domains located between adjacent electroactive material domains can serve to restrict the length scale of the continuous electroactive material domains within the composite particles.

[0058] The electroactive material domains and the modifying material domains can be discrete domains with a distinct boundary between them, or there can be a compositional gradient between the electroactive material domains and the modifying material domains. The modifying material domains can be a coating (such as a film) on the surface of at least some or all of the electroactive material domains. The modifying material domains can be chemically bonded (e.g., covalently, ionically, or metallically) to the electroactive material domains. For example, the modifying material domains can include a passivation layer at the surface of the electroactive material domains, or an alloy of the electroactive material at the surface of the electroactive material domains, or a doped electroactive material at the surface of the electroactive material domains. Alternatively, the modifying material domains can not be chemically bonded to the electroactive material domains. For example, the modifying material can comprise a solid electrolyte or an inert filler, or consist of a solid electrolyte or an inert filler.

[0059] The modifying material domains can contain one or more of carbon, nitrogen, and / or oxygen.

[0060] The modifying material domains can be passivation layers.

[0061] The modifying material domains can be oxide passivation layers. One type of modifying material is, for example, a native oxide passivation layer formed by exposing the surface of the electroactive material domains to air or other oxygen-containing gases. In the case where the electroactive material domains contain silicon, the modifying material domains can contain silicon oxide of the formula SiO x where 0 < x ≤ 2. The silicon oxide is preferably amorphous silicon oxide.

[0062] The modified material domain can be a nitride passivation layer. Another type of modified material is a nitride passivation layer formed, for example, by exposing the surface of the electroactive material domain to ammonia or other nitrogen-containing molecules. In the case where the electroactive material domain contains silicon, the modified material domain can contain silicon nitride of the formula SiN x where 0 < x ≤ 4 / 3. The silicon nitride is preferably amorphous silicon nitride. Nitride modified materials are superior to oxide modified materials. Because sub-stoichiometric nitrides (such as SiN x where 0 < x ≤ 4 / 3) are conductive, the nitride modified domain acts as a conductive network that allows for faster charging and discharging of the electroactive material. The nitride modified material domain is also thought to improve capacity retention. Phosphine can also be used as a passivating agent, as a phosphorus analogue of ammonia.

[0063] The modified material domain can be an oxynitride passivation layer. Another type of modified material is an oxynitride passivation layer formed, for example, by exposing the surface of the electroactive material domain to ammonia (or other nitrogen-containing molecules) and oxygen. In the case where the electroactive material domain contains silicon, the modified material domain can contain silicon oxynitride of the formula SiO x N y where 0 < x < 2, 0 < y < 4 / 3, and 0 < (2x + 3y) ≤ 4). The silicon nitride is preferably amorphous silicon oxynitride.

[0064] The modified material domain can be a carbide passivation layer. Another type of modified material is a carbide passivation layer. In the case where the electroactive material domain contains silicon, the modified material domain can contain silicon carbide of the formula SiC x where 0 < x ≤ 1. The silicon carbide is preferably amorphous silicon carbide. The silicon carbide layer can be formed by contacting the surface of the electroactive material domain with a carbon-containing precursor (such as methane or ethylene) at an elevated temperature.

[0065] Another type of modified material is a passivation layer containing an organic moiety covalently bonded to at least a portion of the surface in the electroactive material domain. For example, the modified material domain can contain a carbon-containing organic moiety covalently bonded to the surface of the electroactive material domain. For example, the modified material domain can contain a hydrocarbon group covalently bonded to the surface of the electroactive material domain.

[0066] Passivating agents suitable for forming a passivation layer containing an organic moiety include: compounds containing an alkene, alkyne or carbonyl functional group, more preferably compounds containing a terminal alkene, terminal alkyne, aldehyde group or ketone group.

[0067] The covalently bonded organic modified material domains can be formed by inserting an organic compound into the MH groups (wherein M represents an atom of the electroactive material) at the surface of the electroactive material to form a covalently passivated surface resistant to air oxidation. When silicon is the electroactive material, the passivation reaction between the silicon surface and the passivating agent can be understood as a form of hydrosilylation, as schematically shown below.

[0068]

[0069] Replacing the hydride ends at the surface of the electroactive material domains with covalently bonded organic modification material domains (such as carbon-containing organic moieties) is advantageous because the hydride ends may decompose to produce hydrogen gas, which may be detrimental to the electrode morphology. In addition, Si-C bonding is believed to improve conductivity.

[0070] Suitable organic compounds that can be used to form modified material domains by passivation of the surface of the electroactive material domain include compounds containing olefin, alkyne or carbonyl functional groups, more preferably terminal olefin, terminal alkyne or aldehyde groups. For example, the modified material domain can be formed by passivating the surface of the electroactive material domain using one or more compounds having the following formula:

[0071] Preferred passivating agents include one or more compounds having the formula:

[0072] (i)R 1 -CH=CH-R 1 ;

[0073] (ii) R 1 -C≡CR 1 ;as well as

[0074] (iii) O=CR 1 R 1 ;

[0075] Each R 1 independently represent H or an unsubstituted or substituted aliphatic or aromatic hydrocarbon group having 1 to 20 carbon atoms, or wherein two R 1 The groups form unsubstituted or substituted ring structures containing from 3 to 8 carbon atoms in the ring.

[0076] The modifying material may be a hydrocarbon group covalently bonded to the surface of at least a portion of the electroactive material domain. The modifying material may be a C 2-22 The modifying material may be a saturated or unsaturated C 2-22The modifying material may be a linear or branched C 2-22 The modifying material may be a monocyclic or polycyclic C 2-22 The modifying material may be a C-group covalently bonded to the surface of at least a portion of the electroactive material domain. 2-22 Alkyl, C 2-22 Alkenyl, C 2-22 Alkynyl, C 3-22 Cycloalkyl, C 3-22 Cycloalkenyl, C 3-22 Cycloalkynyl or C 6-22 The modifying material may be selected from the group consisting of:

[0077]

[0078] It is to be understood that the bonds shown as being crossed by a dashed line are bonded to atoms on the surface of the electroactive material domain. For example, when the electroactive material is silicon, the bonds shown as being crossed by a dashed line are bonded to Si.

[0079] Particularly preferred passivating agents include one or more compounds having the formula:

[0080] (i) CH2=CH-R 1 ;and

[0081] (ii) HC≡CR 1 ;

[0082] Where R 1 As defined above. Preferably, R 1 is unsubstituted.

[0083] Specific examples of suitable organic compounds that can be used to form modified material domains by passivation of the surface of the electroactive material domain include: ethylene, propylene, 1-butene, butadiene, 1-pentene, 1,4-pentadiene, 1-hexene, 1-octene, styrene, divinylbenzene, acetylene, phenylacetylene, norbornene, norbornadiene, and bicyclo[2.2.2]oct-2-ene. Mixtures of different passivating agents can also be used.

[0084] Other examples of organic compounds that can be used to form modified material domains by passivation of the surface of the electroactive material domain include compounds containing active hydrogen atoms bonded to oxygen, nitrogen, sulfur or phosphorus. For example, the passivating agent can be an alcohol, an amine, a thiol or a phosphine. The reaction of the group -XH with the hydride group at the surface of the electroactive material is understood to result in the elimination of H2 and the formation of a direct bond between X and the surface of the electroactive material.

[0085] Suitable deactivators within this class include compounds having the formula:

[0086] (iv)HX-R 2 ,and

[0087] (v)HX-C(O)-R 1 ,

[0088] Where X represents O, S, NR 1 or PR 1 ; Each R 1 are independently as defined above; and R 2 represents an unsubstituted or substituted aliphatic or aromatic hydrocarbon group having 1 to 20 carbon atoms, or R 1 and R 2 Together they form an unsubstituted or substituted ring structure comprising 3 to 8 carbon atoms in the ring.

[0089] Preferably, X represents O or NH. Particularly preferably, X represents NH.

[0090] Preferably, R 2 represents an optionally substituted aliphatic or aromatic group having 2 to 10 carbon atoms. The amine group may also be incorporated into a 4-10 membered aliphatic or aromatic ring structure, as in pyrrolidine, pyrrole, imidazole, piperazine, indole or purine.

[0091] As another alternative, the modified material domain may comprise a pyrolytic carbon material. As discussed in more detail below, the pyrolytic carbon domain may be formed by CVI using a suitable carbon-containing precursor. The use of pyrolytic carbon materials is advantageous in significantly reducing the surface area of ​​the composite particles, which is believed to improve cycle life and maintain capacity.

[0092] As another alternative, the modified material domain can be a conductive metal or metal alloy. As discussed in more detail below, a conductive metal or metal alloy domain can be formed by CVI using a suitable metal-containing precursor. Examples of suitable conductive metals include silver, gold, copper and titanium.

[0093] As another alternative, the modified material domain may comprise an electroactive material comprising a dopant selected from the group consisting of boron, aluminum, gallium, indium, phosphorus, arsenic, antimony and bismuth. The dopant is preferably boron or phosphorus. The electroactive material may be the same as the electroactive material in the electroactive material domain, or it may be different. The electroactive material may be selected from the group consisting of elemental silicon, elemental tin, elemental germanium, elemental aluminum and mixtures and alloys thereof. The preferred electroactive material is silicon.

[0094] As another alternative, the modified material domain may comprise or consist of a solid electrolyte. The solid electrolyte may be an organic solid electrolyte or an inorganic solid electrolyte.

[0095] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups.

[0096] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts (such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4).

[0097] As another alternative, the modifying material domain may comprise or consist of an inert filler.

[0098] It is preferred that the modifying material does not contain oxygen. The use of modifying materials that do not contain oxygen is believed to help provide composite particles with a low total oxygen content, which is believed to reduce first cycle losses, improve conductivity, improve cycle life, and maintain capacity. Examples of modifying materials that do not contain oxygen include: nitride passivation layers, carbide passivation layers, hydrocarbon groups covalently bonded to the surface of the electroactive material domains, pyrolytic carbon materials, conductive metals or metal alloys, electroactive materials containing dopants, solid electrolytes, and inert fillers.

[0099] In a preferred embodiment, the modifying material is a hydrocarbon group (such as C 2-22 Hydrocarbon groups), or a nitride passivation layer as described herein. These modified materials are believed to provide lower overall oxygen content, improved conductivity, and reduced chemical reactivity of the electroactive material domains.

[0100] The composite particles may optionally also include an external modifying material domain between the outermost electroactive material domain and the outside of the composite particles. These modifying material domains form a barrier between the electroactive material and the outside of the composite particles, thereby inhibiting electrolyte contact with the outermost electroactive material domain, otherwise SEI is easily formed. The external modifying material domain can be formed by any of the modifying materials described herein. A preferred modifying material for the external modifying material domain is a pyrolytic carbon material. Another preferred modifying material for the external modifying material domain is a native oxide of the electroactive material.

[0101] In a preferred embodiment, the particulate material of the present invention comprises a plurality of elemental silicon domains (as electroactive domains) and a plurality of modifying material domains disposed within the internal pore volume of the porous particle skeleton, wherein the modifying material domain comprises a passivation layer comprising an organic moiety, the organic moiety being located between adjacent elemental silicon domains and covalently bonded to the surface of at least a portion of the elemental silicon domains. The composite particle may also comprise an external modifying material domain, the external modifying material domain being a silicon oxide domain.

[0102] In another preferred embodiment, the particulate material of the present invention comprises a plurality of elemental silicon domains (as electroactive domains) and a plurality of pyrolytic carbon domains disposed within the internal pore volume of the porous particle skeleton, wherein at least a portion of the pyrolytic carbon domains are located between adjacent elemental silicon domains. The composite particles may also include an external modifying material domain, wherein the external modifying material domain is a silicon oxide domain.

[0103] In another preferred embodiment, the particulate material of the present invention comprises a plurality of elemental silicon domains (as electroactive domains) and a plurality of metal or metal alloy domains disposed within the internal pore volume of the porous particle skeleton, wherein at least a portion of the metal or metal alloy domains are located between adjacent elemental silicon domains. The composite particles may also comprise an external modifying material domain, wherein the external modifying material domain is a silicon oxide domain.

[0104] The present invention can use a range of different loadings of electroactive material in the composite particles. For example, the amount of electroactive material in the composite particles can be in the range of 5 wt % to 85 wt %, based on the total mass of the composite particles. Preferably, the amount of electroactive material in the composite particles is 10 wt % to 85 wt %, or 15 wt % to 85 wt %, or 20 wt % to 80 wt %, or 25 wt % to 80 wt %, or 30 wt % to 75 wt %, or 35 wt % to 75 wt %, or 40 wt % to 70 wt %, or 45 wt % to 65 wt %, based on the total mass of the composite particles.

[0105] The composite particles may comprise from 40 to 70 wt%, or from 45 to 70 wt%, or from 48 to 70 wt%, or from 50 to 70 wt%, or from 40 to 65 wt%, or from 45 to 65 wt%, or from 48 to 65 wt%, or from 50 to 65 wt%, or from 40 to 60 wt%, or from 45 to 60 wt%, or from 48 to 60 wt%, or from 50 to 60 wt% electroactive material, based on the total mass of the composite particles.

[0106] Preferably, the composite particles comprise 10 wt % to 85 wt %, or 15 wt % to 85 wt %, or 20 wt % to 80 wt %, or 25 wt % to 80 wt %, or 30 wt % to 75 wt %, or 35 wt % to 75 wt %, or 40 wt % to 70 wt %, or 45 wt % to 65 wt % silicon, based on the total mass of the composite particles.

[0107] The composite particles may comprise 40 to 70 wt%, or 45 to 70 wt%, or 48 to 70 wt%, or 50 to 70 wt%, or 40 to 65 wt%, or 45 to 65 wt%, or 48 to 65 wt%, or 50 to 65 wt%, or 40 to 60 wt%, or 45 to 60 wt%, or 48 to 60 wt%, or 50 to 60 wt% silicon, based on the total mass of the composite particles.

[0108] The amount of electroactive material (e.g., silicon) in the composite particles can be selected so that at least 25% and up to 90% or more of the internal pore volume of the porous particle skeleton is occupied by the electroactive material. For example, the electroactive material (e.g., silicon) can occupy 25% to 80%, or 25% to 60%, or 25% to 55%, or 30% to 50%, or 53% to 55%, or 40% to 60%, or 25% to 45%, or 25% to 40% of the internal pore volume of the porous particle skeleton. Within these preferred ranges, the pore volume of the porous particle skeleton effectively accommodates the expansion of the electroactive material (e.g., silicon) during charge and discharge, but avoids excessive pore volume, which is detrimental to the volumetric capacity of the particle particles. However, the amount of electroactive material is not so high as to hinder effective lithiation due to insufficient metal ion diffusion rate or mechanical resistance to lithiation due to insufficient expansion volume.

[0109] In the case where the electroactive material is silicon, the mass ratio of silicon to the conductive porous particle skeleton is required to be within [0.5×P 1 To 1.9×P 1 ]:1, the amount of silicon in the composite particles can be related to the available pore volume, where P 1is the total pore volume of micropores and mesopores in the porous particle skeleton (in cm 3 / g) (for example, if the total volume of the micropores and mesopores of the porous particle or porous particle framework is 1.2 cm 3 / g, then P 1 = 1.2). This relationship takes into account the density of silicon and the pore volume of the porous particle skeleton to define a weight ratio of silicon at which the occupied pore volume is approximately 20% to 82%.

[0110] The amount of electroactive material (e.g., silicon) in the composite particles can be determined by elemental analysis. Elemental analysis can be used to determine the composition of the porous particles that form the porous particle skeleton alone, as well as the composition of the composite particles containing the electroactive material. For example, determining the weight percent of carbon in individual porous carbon particles takes into account the possibility that the porous carbon particles contain small amounts of heteroatoms. The two measurements taken together enable reliable determination of the weight percent of electroactive material (e.g., silicon) relative to the porous carbon particles.

[0111] The silicon content is preferably determined by ICP-OES (Inductively Coupled Plasma - Optical Emission Spectroscopy). A variety of ICP-OES instruments are commercially available, such as The carbon content (and, if desired, the hydrogen content, nitrogen content and oxygen content) of the composite particles and the individual porous carbon particles is preferably determined by IR absorption. A suitable instrument for determining the carbon content, hydrogen content, nitrogen content and oxygen content is Micro Elemental Analyzer (available from Leco Corporation).

[0112] At least 85% by weight of the mass of the electroactive material in the composite particles can be located within the internal pore volume of the porous particle skeleton. Preferably at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the mass of the electroactive material (e.g., silicon) in the composite particles is located within the internal pore volume of the porous particle skeleton, so that no or very little electroactive material (e.g., silicon) is located on the outer surface of the composite particles. The reaction kinetics of the CVI process ensure that preferential deposition of the electroactive material (e.g., silicon) occurs on the inner surface of the porous particles.

[0113] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous particle skeleton or as an oxide layer on any exposed silicon surface. Preferably, the total oxygen content of the composite particles is less than 15 wt%, more preferably less than 10 wt%, more preferably less than 5 wt%, such as less than 4 wt%, or less than 3 wt%, or less than 2 wt%, or less than 1 wt%, or less than 0.5 wt%, based on the total mass of the composite particles. Preferably, the total oxygen content of the composite particles is less than 5 wt%, or less than 4 wt%, or less than 3 wt%, or less than 2 wt%, or less than 1 wt%, or less than 0.5 wt%, based on the total mass of the composite particles.

[0114] The composite particles may comprise a ratio of total oxygen content to silicon content of 0.1:1 or less, based on the total mass of the composite particles.

[0115] The composite particles preferably have a low total chlorine content. Chlorine may be present in the composite particles, for example as part of a byproduct of deposition of the electroactive material. Preferably, the total chlorine content of the composite particles is less than 100 ppm, or less than 90 ppm, or less than 80 ppm, or less than 70 ppm, based on the total mass of the composite particles. Without being bound by theory, it is believed that chlorine is an impurity in the composite particles that is detrimental to battery performance.

[0116] The composite particles preferably have a low total content of transition metals and / or alkali metals. For example, the total content of transition metals and alkali metals in the composite particles may be less than 0.5 wt % based on the total weight of the composite particles.

[0117] Optionally, the composite particles comprise 0.0001 wt % to 0.5 wt %, such as 0.001 wt % to 0.1 wt % zirconium, based on the total mass of the composite particles.

[0118] D of composite particles 50 The particle size is preferably in the range of 0.5 to 30 μm. The D 50 In case the particle size is greater than 30 μm, it is preferably prepared by grinding the composite particles to a particle size of no more than 30 μm, for example, before the composite particles are used to prepare electrodes. 50 Particle size is used to reduce the size of composite particles. 50 Composite particles with a particle size of no more than 30 μm have good dispersibility in slurry, structural robustness, high capacity retention after repeated charge-discharge cycles, and are suitable for forming a dense electrode layer with a uniform thickness in the conventional thickness range of 20 to 50 μm.

[0119] Optionally, the D of the composite particle 50 The particle size may be at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. Optionally, D50 The particle size may be no greater than 20 μm, or no greater than 18 μm, or no greater than 16 μm, or no greater than 14 μm, or no greater than 12 μm, or no greater than 10 μm, or no greater than 8 μm.

[0120] For example, the D of a composite particle 50 The particle size may be in the range of 1 to 25 μm, or in the range of 1 to 20 μm, or in the range of 1 to 18 μm, or in the range of 1 to 16 μm, or in the range of 2 to 16 μm, or in the range of 2 to 14 μm, or in the range of 2 to 12 μm, or in the range of 2 to 10 μm, or in the range of 2 to 8 μm.

[0121] D of composite particles 10 The particle size is preferably at least 0.5 μm, or at least 0.8 μm, or at least 1 μm. 10 The particle size is maintained above 0.5 μm, reducing the possibility of undesirable agglomeration of submicron sized particles, resulting in improved dispersion of the particulate material and improved capacity retention.

[0122] D of composite particles 90 The particle size is preferably no more than 50 μm, or no more than 40 μm, or no more than 30 μm, or no more than 25 μm, or no more than 20 μm, or no more than 15 μm. The presence of very large particles leads to uneven filling of particles in the electrode active layer, thereby destroying the formation of a dense electrode layer, especially an electrode layer with a thickness in the range of 20 to 50 μm. Therefore, it is preferred that D 90 The particle size is at most 40 μm, and more preferably even smaller.

[0123] The composite particles preferably have a narrow size distribution span. For example, the particle size distribution span (defined as (D 90 -D 10 ) / D 50 ) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow size distribution span, efficient filling of particles into a dense electrode layer can be more easily achieved.

[0124] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, wherein the particle volume is understood to include the volume of any intra-particle pores. 50 ” and “D 50 The term "particle size" as used herein refers to the volume median particle size, i.e., the diameter below which 50% of the volume of the particle population is measured. 10 ” and “D 10The term "particle size" as used herein refers to the 10th percentile volume median particle size, i.e., the diameter at which 10% of the volume of the particle population is below a certain diameter. 90 ” and “D 90 The term "particle size" refers to the 90th percentile volume median particle size, i.e., the diameter below which 90% of the volume of the particle population is measured.

[0125] Particle size and particle size distribution can be determined by standard laser diffraction techniques according to ISO 13320:2009. Laser diffraction relies on the principle that particles will scatter light at an angle that varies depending on the size of the particle, and that a collection of multiple particles will produce a scattered light pattern defined by intensity and angle that can be related to the particle size distribution. A variety of laser diffraction instruments are commercially available for rapid and reliable determination of particle size distribution. Unless otherwise stated, particle size distribution measurements indicated or reported herein were obtained by a laser diffraction analyzer from Malvern Instruments. TM The regular Malvern Mastersizer TM Measured by Malvern Mastersizer 3000 particle size analyzer. TM The 3000 particle size analyzer operates by projecting a helium-neon gas laser beam through a transparent cell containing the particles of interest suspended in an aqueous solution. The light impinging on the particles is scattered through angles inversely proportional to the particle size, and an array of photodetectors measures the intensity of the light at a number of predetermined angles, and the measured intensities at different angles are processed by computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values ​​reported herein were calculated using an aqueous solution with 5% by volume of the surfactant SPAN. TM The particle refractive index of the porous particles was considered to be 2.68, and that of the composite particles was considered to be 3.50, and that of the dispersant was considered to be 1.378. The particle size distribution was calculated using the Mie scattering model.

[0126] The total volume of micropores and / or mesopores of the composite particles (measured by nitrogen adsorption as described herein) is preferably no more than 0.35 cm 3 / g, or not more than 0.25cm 3 / g, or not more than 0.15cm 3 / g, or not more than 0.1cm 3 / g, or not more than 0.05cm 3 / g, or not more than 0.03cm 3 / g, or not more than 0.02cm 3 / g. Preferably, the total volume of the micropores and / or mesopores of the composite particles does not exceed 20% by volume of the total volume of the micropores and / or mesopores of the porous particle skeleton, more preferably does not exceed 15% by volume, or does not exceed 10% by volume, or does not exceed 5% by volume. The lower total volume of micropores and / or mesopores in the composite particles reduces the penetration of the electrolyte solvent into the composite particles that causes the internal formation of SEI, and generally reduces the surface area, thereby providing better control to avoid undesirable surface reactions when used.

[0127] The BET surface area of ​​the composite particles preferably does not exceed 300 m 2 / g, or not more than 250m 2 / g, or not more than 200m 2 / g, or not more than 150m 2 / g. More preferably, no more than 100m 2 / g, or not more than 80m 2 / g, or not more than 60m 2 / g, or not more than 50m 2 / g, or not more than 40m 2 / g, or not more than 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g, or not more than 5m 2 / g. Preferably, the BET surface area of ​​the composite particles does not exceed 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g, or not more than 5m 2 / g. Generally, a low BET surface area is preferred to minimize the formation of a solid electrolyte interface (SEI) layer at the surface of the composite particles during the first charge-discharge cycle of the anode. However, too low a BET surface area leads to unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to the metal ions in the surrounding electrolyte. For example, the BET surface area can be between 0.1 and 100 m 2 / g, or 0.1 to 80m 2 / g, or 0.5 to 60m 2 / g, or 0.5 to 40m 2 / g, or 1 to 30m 2 / g, or 1 to 25m 2 / g, or 2 to 20m 2 / g range.

[0128] The shape of the composite particles can be irregular or spherical. Spherical particles as defined herein can include both spherical particles and ellipsoidal particles, and the shape of the composite particles of the present invention can be suitably defined with reference to the sphericity and aspect ratio of the particles of the present invention. It is found that spherical particles are particularly well suited for dispersions in slurries without forming agglomerates. In addition, it is unexpectedly found that the use of porous spherical particles provides a further improvement in strength when compared to porous particles and porous particle fragments of irregular morphology.

[0129] The sphericity of an object is conventionally defined as the ratio of the surface area of ​​a sphere to the surface area of ​​an object, wherein the object and the sphere have the same volume. However, it is actually difficult to measure the surface area and volume of individual particles at micrometer scale. However, highly accurate two-dimensional projections of micrometer-scale particles can be obtained by scanning electron microscopy (SEM) and by dynamic image analysis, wherein a digital camera is used to record the shadow of the particle projection. The term "sphericity" as used herein should be understood as the ratio of the area of ​​a particle projection to the area of ​​a circle, wherein the particle projection and the circle have the same perimeter. Therefore, for individual particles, the sphericity S can be defined as:

[0130]

[0131] Among them A m is the measured area of ​​the particle projection, and C m is the measured circumference of the particle projection. As used herein, the average sphericity S of a plurality of particles av is defined as:

[0132]

[0133] Where n represents the number of particles in the population.

[0134] As used herein, the term "quasi-spherical" as applied to the composite particles of the present invention is understood to refer to materials having an average sphericity of at least 0.70. Preferably, the average sphericity of the composite particles of the present invention is at least 0.85, more preferably at least 0.90, more preferably at least 0.92, more preferably at least 0.93, more preferably at least 0.94, more preferably at least 0.95. Optionally, the average sphericity of the composite particles may be at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.

[0135] It is to be understood that in the case of any particle that is not a perfect spherical shape, the perimeter and area of ​​the two-dimensional particle projection will depend on the direction of the particle. However, the effect of particle direction can be offset by reporting the sphericity and aspect ratio of the average value obtained by multiple particles in random directions. A variety of SEM and dynamic image analysis instruments are commercially available, making it possible to quickly and reliably determine the sphericity and aspect ratio of particulate materials. Unless otherwise stated, the sphericity values ​​as specified or reported herein are measured by the CamSizer XT particle analyzer from Retsch Technology GmbH. The CamSizerXT is a dynamic image analysis instrument that can obtain highly accurate distributions of the size and shape of particulate materials with sample volumes of 100 mg to 100 g, making it possible to directly calculate properties such as average sphericity and aspect ratio by the instrument.

[0136] The composite particles may be further characterized by their performance in thermogravimetric analysis (TGA) in air. This analytical method relies on the principle that an increase in weight is observed when an electroactive material is oxidized in air and at elevated temperatures.

[0137] As defined herein, "surface silicon" is determined by the initial mass increase in the TGA trace from a minimum value at 150°C to 500°C to a maximum mass measured in the temperature range of 550°C to 650°C, wherein the TGA is performed in air at a heating rate of 10°C / min. This mass increase is believed to be due to oxidation of the surface silicon, thus enabling the determination of the percentage of surface silicon as a proportion of the total amount of silicon according to the following formula:

[0138] Y=1.875×[(M max –M min ) / M f ]×100%

[0139] Where Y is the percentage of surface silicon (as a proportion of the total silicon in the sample), M max is the maximum mass of the sample measured in the temperature range of 550°C to 650°C, M min is the minimum mass of the sample above 150°C and below 500°C, and M f is the mass of the sample at the completion of oxidation at 1400°C. For completeness, it should be understood that 1.875 is the molar mass ratio of SiO2 to O2 (i.e. the mass ratio of SiO2 formed to the mass increase due to the addition of oxygen). Typically, TGA analysis is performed using a sample amount of 10 mg ± 2 mg.

[0140] It has been found that when the surface silicon measured by the above TGA method is at least 20% by weight of the total amount of silicon in the material, the reversible capacity retention over multiple charge / discharge cycles is significantly improved. Preferably, at least 22% by weight, or at least 25% by weight, at least 30% by weight of silicon, or at least 35% by weight of silicon, or at least 40% by weight of silicon, or at least 45% by weight of silicon is surface silicon as measured by thermogravimetric analysis (TGA).

[0141] In addition to a high surface silicon content, the particulate material of the present invention preferably has a low bulk silicon content as determined by TGA. Bulk silicon is defined herein as silicon that oxidizes above 800°C as determined by TGA, wherein TGA is conducted in air at a heating rate of 10°C / min. Thus, the bulk silicon content is determined according to the following formula:

[0142] Z=1.875×[(M f -M 800 ) / M f ]×100%

[0143] Where Z is the percentage of silicon that is not oxidized at 800°C, M 800 is the mass of the sample at 800 °C, and M f is the mass of ash at the completion of oxidation at 1400°C. For the purpose of this analysis, it is assumed that any mass increase above 800°C corresponds to oxidation of silicon to SiO2, and the total mass at the completion of oxidation is SiO2. Typically, TGA analysis is performed using a sample size of 10 mg ± 2 mg.

[0144] Silicon that oxidizes above 800° C. is less desirable. Preferably, no more than 10 wt%, or no more than 8 wt%, or no more than 6 wt%, or no more than 5 wt%, or no more than 4 wt%, or no more than 3 wt%, or no more than 2 wt%, or no more than 1.5 wt% of the silicon is gross phase silicon as determined by TGA.

[0145] Preferably, at least 20 wt% of the silicon is surface silicon and no more than 10 wt% of the silicon is rough phase silicon, both of which are determined by TGA. More preferably, at least 30 wt% of the silicon is surface silicon and no more than 10 wt% of the silicon is rough phase silicon, both of which are determined by TGA. More preferably, at least 35 wt% of the silicon is surface silicon and no more than 8 wt% of the silicon is rough phase silicon, both of which are determined by TGA. More preferably, at least 40 wt% of the silicon is surface silicon and no more than 5 wt% of the silicon is rough phase silicon, both of which are determined by TGA. More preferably, at least 45 wt% of the silicon is surface silicon and no more than 2 wt% of the silicon is rough phase silicon, both of which are determined by TGA.

[0146] The composite particles preferably have a specific charge capacity of 1200 to 2340 mAh / g upon initial lithiation. Preferably, the composite particles have a specific charge capacity of at least 1400 mAh / g upon initial lithiation.

[0147] The composite particles may include a coating of a lithium ion permeable material, such as a carbon coating. The lithium ion permeable material coating has the following advantages: it further reduces the BET surface area of ​​the composite particles by smoothing any surface defects and by filling any residual surface micropores, thereby further reducing the first cycle loss. In addition, the lithium ion permeable material coating improves the conductivity of the surface of the composite particles, thereby reducing the need for conductive additives in the electrode composition, and also creates an optimal surface for forming a stable SEI layer, thereby improving the capacity retention rate during cycling.

[0148] The reduction in the surface area of ​​the composite particles also has the effect of reducing the amount of binder required to form an electrode active layer comprising the composite particles. Excess binder is known to promote reduced rate performance. Another advantage of the present invention is that the filler contributes to the improvement of the compressive strength of the composite particles by providing structural reinforcement of the porous particle skeleton.

[0149] When a carbon coating is present, the BET surface area of ​​the composite particles preferably does not exceed 150 m 2 / g, or not more than 100m 2 / g, or not more than 80m 2 / g, or not more than 60m 2 / g, or not more than 40m 2 / g, or not more than 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g, or not more than 5m 2 / g, or not more than 3m 2 / g.

[0150] In a second aspect, the present invention provides a method for preparing composite particles, the method comprising the following steps:

[0151] (a) providing a plurality of porous particles including micropores and / or mesopores, wherein the total pore volume of the micropores and mesopores measured by gas adsorption is in the range of 0.4 to 2.2 cm 3 / g range;

[0152] (b) contacting the porous particle with a precursor of an electroactive material at a temperature effective to cause deposition of a plurality of electroactive material domains in the pores of the porous particle;

[0153] (c) forming a plurality of modified material domains in the pores of the porous particle and adjacent to the electroactive material domains deposited in step (b);

[0154] (d) contacting the particles from step (c) with a precursor of an electroactive material at a temperature effective to cause deposition of additional electroactive material domains in the pores of the porous particles and adjacent to the modified material domains formed in step (c).

[0155] Thus, the method of the present invention is a multi-step method comprising, in sequence: a first step of depositing an electroactive material, a step of forming a modified material adjacent to the electroactive material, and a further step of depositing an electroactive material adjacent to the modified material. The result of this sequence of steps is that at least a portion of the modified material domains in the product from step (d) are located between the electroactive material domains deposited in step (b) and the electroactive material domains deposited in step (d). Thus, the product of the method of the second aspect of the present invention is a particulate material according to the first aspect of the present invention.

[0156] As discussed above, the porous particles used in step (a) form the porous particle skeleton in the composite particles. The term "porous particle skeleton" is used in the context of a composite particle product, while the term "porous particle" is used to describe the starting material that ultimately forms the porous particle skeleton. Therefore, the porous particles used in step (a) of the method of the second aspect of the invention may have any of the features described herein for the porous particle skeleton in the context of the first aspect of the invention. The features of the porous particle skeleton may optionally be combined with any of the additional features of the porous particles listed below.

[0157] Usually, the D of porous particles 50 The particle size may be in the range of 0.5 to 200 μm. Optionally, the D 50 The particle size may be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. Optionally, the D 50 The particle size may be no more than 150 μm, or no more than 100 μm, or no more than 70 μm, or no more than 50 μm, or no more than 40 μm, or no more than 30 μm, or no more than 25 μm, or no more than 20 μm, or no more than 18 μm, or no more than 15 μm, or no more than 12 μm, or no more than 10 μm, or no more than 8 μm.

[0158] For example, the D 50The particle size may be in the range of 0.5 to 150 μm, or 0.5 to 100 μm, or 0.5 to 50 μm, or 0.5 to 30 μm, or 1 to 25 μm, or 1 to 20 μm, or 2 to 25 μm, or 2 to 20 μm, or 2 to 18 μm, or 2 to 15 μm, or 2 to 12 μm, or 2.5 to 15 μm, or 2.5 to 12 μm, or 2 to 10 μm, or 3 to 20 μm, or 3 to 18 μm, or 3 to 15 μm, or 4 to 18 μm, or 4 to 15 μm, or 4 to 12 μm, or 5 to 15 μm, or 5 to 12 μm, or 5 to 10 μm, or 5 to 8 μm. Particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for making composite particles for use in anodes of metal ion batteries by the CVI process.

[0159] D of porous particles 10 The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 The particle size is maintained above 0.2 μm, reducing the possibility of undesirable agglomeration of submicron-sized particles and improving the dispersibility of the formed composite particles.

[0160] D of porous particles 90 The particle size is preferably no more than 300 μm, or no more than 250 μm, or no more than 200 μm, or no more than 150 μm, or no more than 100 μm, or no more than 80 μm, or no more than 60 μm, or no more than 40 μm, or no more than 30 μm, or no more than 25 μm, or no more than 20 μm.

[0161] The porous particles preferably have a narrow size distribution span. For example, the particle size distribution span (defined as (D 90 -D 10 ) / D 50 ) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow size distribution span, efficient packing of particles into a dense powder bed can be more easily achieved.

[0162] The BET surface area of ​​the porous particles is preferably at least 100 m 2 / g, or at least 500m 2 / g, or at least 750m 2 / g, or at least 1,000m 2 / g. The term "BET surface area" as used herein should be taken to mean the surface area per unit mass calculated from the measurement results of the physical adsorption of gas molecules on the solid surface using the Brunauer-Emmett-Teller principle according to ISO 9277. Preferably, the BET surface area of ​​the porous particles does not exceed 4,000 m 2 / g, or not more than 3,500m 2 / g, or not more than 3,250m 2 / g, or not more than 3,000m 2 / g, or not more than 2,500m 2 / g, or not more than 2,000m 2 / g. For example, the BET surface area of ​​a porous particle can be 100m 2 / g to 4,000m 2 / g, or 500m 2 / g to 4,000m 2 / g, or 750m 2 / g to 3,500m 2 / g, or 1,000m 2 / g to 3,250m 2 / g、1,000m 2 / g to 3,000m 2 / g, or 1,000m 2 / g to 2,500m 2 / g, or 1,000m 2 / g to 2,000m 2 / g range.

[0163] The average sphericity (as defined above) of the porous particles may exceed 0.5. Preferably, their average sphericity is at least 0.55, or at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85. Preferably, the average sphericity of the porous particles is at least 0.90, or at least 0.92, or at least 0.93, or at least 0.94, or at least 0.95.

[0164] Preferably, the porous particles have:

[0165] (i) 0.4 to 2.2 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0166] (ii) PD no larger than 20nm 50 Pore ​​size, preferably no more than 30nm PD 90 Pore ​​size, preferably no more than 15 nm PD 30 Aperture; and

[0167] (iii) D in the range of 0.5 to 30 μm 50 particle size; and optionally

[0168] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0169] More preferably, the porous particles have:

[0170] (i) 0.6 to 1.8 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0171] (ii) PDs not exceeding 10nm 50 Pore ​​size, preferably no more than 20 nm PD 90 Pore ​​size, preferably no more than 8nm PD 30 Aperture; and

[0172] (iii) D in the range of 1 to 25 μm 50 particle size; and optionally

[0173] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0174] More preferably, the porous particles have:

[0175] (i) 0.7 to 1.6 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0176] (ii) PDs not exceeding 10nm 50 Pore ​​size, preferably no more than 20 nm PD 90 Pore ​​size, preferably no more than 8nm PD 30 Aperture; and

[0177] (iii) D in the range of 1 to 20 μm 50 particle size; and optionally

[0178] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0179] More preferably, the porous particles have:

[0180] (i) 0.7 to 1.5 cm3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0181] (ii) PD no larger than 5nm 50 Pore ​​size, preferably no more than 10 nm PD 90 Pore ​​size, preferably no more than 3nm PD 30 Aperture; and

[0182] (iii) D in the range of 2 to 20 μm 50 particle size; and optionally

[0183] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0184] More preferably, the porous particles have:

[0185] (i) 0.7 to 1.4 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0186] (ii) PD no larger than 5nm 50 Pore ​​size, preferably no more than 10 nm PD 90 Pore ​​size, preferably no more than 3nm PD 30 Aperture; and

[0187] (iii) D in the range of 2 to 20 μm 50 particle size; and optionally

[0188] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0189] More preferably, the porous particles have:

[0190] (i) 0.7 to 1.4 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0191] (ii) PD no larger than 5nm 50 Pore ​​size, preferably no more than 10 nm PD 90 Pore ​​size, preferably no more than 3nm PD 30 Aperture; and

[0192] (iii) D in the range of 2 to 18 μm 50 particle size; and optionally

[0193] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0194] More preferably, the porous particles have:

[0195] (i) 0.7 to 1.4 cm 3 The total pore volume of micropores and mesopores measured by nitrogen adsorption in the range of 1 / g;

[0196] (ii) PD no larger than 2nm 50 Pore ​​size, preferably no more than 5 nm PD 90 Pore ​​size, preferably no more than 1 nm PD 30 Aperture; and

[0197] (iii) D in the range of 2 to 15 μm 50 particle size; and optionally

[0198] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0199] Composite particles can have:

[0200] (i) D of at least 0.5 μm 10 Particle size;

[0201] (ii) D not exceeding 50 μm 90 Particle size; and

[0202] (iii) not more than 0.35 cm 3 / g of the total volume of micropores and mesopores; and optionally

[0203] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0204] Composite particles can have:

[0205] (i) D of at least 0.8 μm 10 Particle size;

[0206] (ii) D not exceeding 40 μm 90 Particle size; and

[0207] (iii) not more than 0.35 cm 3 / g of the total volume of micropores and mesopores; and optionally

[0208] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0209] Composite particles can have:

[0210] (i) D of at least 0.8 μm 10 Particle size;

[0211] (ii) D not exceeding 30 μm 90 Particle size; and

[0212] (iii) not more than 0.35 cm 3 / g of the total volume of micropores and mesopores; and optionally

[0213] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0214] Composite particles can have:

[0215] (i) D of at least 1 μm 10 Particle size;

[0216] (ii) D not exceeding 25 μm 90 Particle size; and

[0217] (iii) not more than 0.25 cm 3 / g of the total volume of micropores and mesopores; and optionally

[0218] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0219] Composite particles can have:

[0220] (i) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0221] (ii) 40 wt % to 70 wt % silicon, based on the total mass of the composite particle; and

[0222] (iii) not more than 30m 2 / g of BET surface area; and optionally

[0223] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0224] Composite particles can have:

[0225] (i) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0226] (ii) 40 to 60 wt % silicon, based on the total mass of the composite particle; and

[0227] (iii) not more than 20m 2 / g of BET surface area; and optionally

[0228] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0229] Composite particles can have:

[0230] (i) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0231] (ii) 40 to 60 wt % silicon, based on the total mass of the composite particle; and

[0232] (iii) not more than 15m 2 / g of BET surface area; and optionally

[0233] (iv) Particle size distribution span (D) below 5 90 -D 10 ) / D 50 ).

[0234] Composite particles having these preferred total oxygen contents, silicon contents, and BET surface areas are believed to have improved cycle life and energy capacity.

[0235] Composite particles can have:

[0236] (i) D of at least 0.5 μm 10 Particle size;

[0237] (ii) D not exceeding 50 μm 90 Particle size;

[0238] (iii) not more than 0.35 cm 3 / g total volume of micropores and mesopores;

[0239] (iv) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0240] (v) 40 to 70 weight percent silicon, based on the total mass of the composite particle; and (vi) no more than 30 m 2 / g BET surface area; and optionally (vii) a particle size distribution span (D 90 -D 10 ) / D 50 ).

[0241] Composite particles can have:

[0242] (i) D of at least 0.8 μm 10 Particle size;

[0243] (ii) D not exceeding 40 μm 90 Particle size;

[0244] (iii) not more than 0.35 cm 3 / g total volume of micropores and mesopores;

[0245] (iv) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0246] (v) 40 to 60 weight percent silicon, based on the total mass of the composite particle; and (vi) no more than 20 m 2 / g BET surface area; and optionally (vii) a particle size distribution span (D 90 -D 10 ) / D 50 ).

[0247] Composite particles can have:

[0248] (i) D of at least 0.8 μm 10 Particle size;

[0249] (ii) D not exceeding 30 μm 90 Particle size;

[0250] (iii) not more than 0.35 cm 3 / g total volume of micropores and mesopores;

[0251] (iv) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0252] (v) 40% to 60% by weight silicon, based on the total mass of the composite particle; and (vi) no more than 15 m 2 / g BET surface area; and optionally (vii) a particle size distribution span (D 90 -D 10 ) / D 50 ).

[0253] Composite particles can have:

[0254] (i) D of at least 1 μm 10Particle size;

[0255] (ii) D not exceeding 25 μm 90 Particle size; and

[0256] (iii) not more than 0.25 cm 3 / g total volume of micropores and mesopores;

[0257] (iv) a total oxygen content of less than 5% by weight based on the total mass of the composite particle;

[0258] (v) 40% to 60% by weight silicon, based on the total mass of the composite particle; and (vi) no more than 15 m 2 / g BET surface area; and optionally (vii) a particle size distribution span (D 90 -D 10 ) / D 50 ).

[0259] The aforementioned preferred features of the porous particles also apply to the porous particle skeleton in the composite particles of the first aspect of the invention.

[0260] The electroactive materials deposited in steps (b) and (d) may be the same or different and may optionally be independently selected from silicon, tin, germanium, aluminum and mixtures and alloys thereof. The preferred electroactive material is silicon. Preferably, the electroactive material deposited in at least one of steps (b) and (d) is silicon. More preferably, the electroactive material deposited in each of steps (b) and (d) is silicon.

[0261] Suitable silicon precursors include monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8), butadienesilane (Si4H 10 ), methylsilane (CH3SiH3), dimethylsilane ((CH3)2SiH2) or chlorosilanes such as trichlorosilane (HSiCl3) or methylchlorosilanes such as methyltrichlorosilane (CH3SiCl3) or dimethyldichlorosilane ((CH3)2SiCl2). A preferred silicon precursor is monosilane.

[0262] Suitable tin precursors include: bis[bis(trimethylsilyl)amino]tin(II) ([[(CH3)3Si]2N]2Sn), tetraallyltin ((H2C=CHCH2)4Sn), tetra(diethylamino)tin(IV) ([(C2H5)2N]4Sn), tetra(dimethylamino)tin(IV) ([(CH3)2N]4Sn), tetramethyltin (Sn(CH3)4), tetravinyltin (Sn(CH=CH2)4), acetylacetonatetin(II) (C2H5)2N]4Sn, 10 H 14O4Sn), trimethyl(phenylethynyl)tin (C6H5C≡CSn(CH3)3) and trimethyl(phenyl)tin (C6H5Sn(CH3)3). A preferred tin precursor is tetramethyltin.

[0263] Suitable aluminum precursors include tris(2,2,6,6-tetramethyl-3,5-heptanedione)aluminum (Al(OCC(CH3)3CHCOC(CH3)3)3), trimethylaluminum ((CH3)3Al) and tris(dimethylamino)aluminum(III) (Al(N(CH3)2)3). A preferred aluminum precursor is trimethylaluminum.

[0264] Suitable germanium precursors include: germanium (GeH4), hexamethylgermanium ((CH3)3GeGe(CH3)3), tetramethylgermanium ((CH3)4Ge), tributylgermanium hydride ([CH3(CH2)3]3GeH), triethylgermanium hydride ((C2H5)3GeH) and triphenylgermanium hydride ((C6H5)3GeH). A preferred germanium precursor is germanium.

[0265] In the case where the precursor is a chlorinated compound such as chlorosilane, the precursor is used in admixture with hydrogen, preferably in an atomic ratio of hydrogen to chlorine of at least 1:1.

[0266] Optionally, the precursor is free of chlorine. Chlorine-free means that the precursor contains less than 1 wt%, preferably less than 0.1 wt%, preferably less than 0.01 wt% of chlorine-containing compounds.

[0267] The precursor in steps (b) and (d) can be used in pure form (or substantially pure form), or as a mixture diluted with an inert carrier gas such as nitrogen or argon. In the case of a mixture diluted with an inert carrier gas, the precursor can be used in an amount within the range of 1% by volume to 95% by volume, or 1% by volume to 85% by volume, or 1% by volume to 70% by volume, or 1% by volume to 50% by volume, or 2% by volume to 40% by volume, or 5% by volume to 30% by volume, or 5% by volume to 25% by volume based on the total gas volume of the precursor and the inert carrier gas. According to the conventional procedure of working in an inert gas, the presence of oxygen should be minimized to prevent the inappropriate oxidation of the deposited electroactive material. Preferably, the oxygen content is less than 0.01% by volume, more preferably less than 0.001% by volume, based on the total volume of the gas used in steps (b) and (d).

[0268] The temperature in steps (b) and (d) is any temperature effective to decompose the precursor to form the electroactive material. Preferably, the temperature in steps (b) and (d) is independently in the range of 300 to 800°C, or 350 to 800°C, or 380 to 700°C, or 380 to 650°C, or 380 to 600°C, or 380 to 550°C, or 380 to 500°C, or 400 to 450°C, or 450 to 500°C. More preferably, the temperature of each of steps (b) and (d) is independently in the range of 380-500°C, preferably 420-480°C. Optionally, the temperature is substantially the same in steps (b) and (d).

[0269] The operating pressure in steps (b) and (d) may be below atmospheric pressure, above atmospheric pressure or at atmospheric pressure. Optionally, the pressure of each of steps (b) and (d) is maintained below 200 kPa, or at or below 150 kPa, or at or below 120 kPa, or at or below 110 kPa, or at or below 100 kPa, or at or below 90 kPa, or at or below 80 kPa, or at or below 70 kPa, or at or below 60 kPa, or at or below 50 kPa.

[0270] For example, the pressure in at least step (b) is maintained below 200 kPa, or at or below 150 kPa, or at or below 120 kPa, or at or below 110 kPa, or at or below 100 kPa, or at or below 90 kPa, or at or below 80 kPa, or at or below 70 kPa, or at or below 60 kPa, or at or below 50 kPa.

[0271] Optionally, the pressure of both steps (b) and (d) can be maintained below 200 kPa, or at or below 150 kPa, or at or below 120 kPa, or at or below 110 kPa, or at or below 100 kPa, or at or below 90 kPa, or at or below 80 kPa, or at or below 70 kPa, or at or below 60 kPa, or at or below 50 kPa.

[0272] References to pressure in any step of the claimed process refer to the absolute pressure in the reaction zone which may comprise a reaction vessel of suitable form.

[0273] The deposition of the electroactive material by CVI leads to the elimination of byproducts, particularly byproduct gases such as hydrogen. Step (b) and / or step (d) preferably also include separation of byproducts. The separation of byproducts from the particles formed in step (b) and / or step (d) can be achieved by flushing the reactor with an inert gas and / or discharging the reactor by reducing the pressure. For example, the separation of the intermediate particles formed in the byproduct and step (b) can be achieved by evacuating the reactor to a pressure lower than 100kPa, or lower than 80kPa, or lower than 60kPa, or lower than 40kPa, or lower than 20kPa, or lower than 10kPa, or lower than 5kPa, or lower than 2kPa, or lower than 10kPa. Evacuating the reactor to low pressure can not only effectively remove byproducts in the gas phase, but also effectively desorb any byproducts that may be adsorbed on the surface of the deposited electroactive material.

[0274] The modified material formed in step (c) may optionally be a passivation layer formed on the surface of the electroactive material deposited in step (b). Thus, step (c) may also include contacting the intermediate particles from step (b) with a passivating agent. As described above, the passivating agent is a compound or mixture of compounds that reacts with the surface of the electroactive material deposited in step (b) to form a modified surface. Any of the passivating agents described with respect to the first aspect of the invention may be used in step (c).

[0275] The contacting of the electroactive material with the passivating agent in step (c) may be carried out at a temperature in the range of 25 to 800°C, preferably in the range of 50 to 500°C, more preferably in the range of 100 to 300°C.

[0276] The formation of the native oxide layer is exothermic and therefore requires careful process control to prevent overheating or even combustion of the particulate material. Where the modified material formed in step (c) is a native oxide layer, step (c) may comprise cooling the material formed in step (b) to a temperature below 300°C, preferably below 200°C, optionally below 100°C, prior to contacting the surface of the electroactive material domains with the oxygen-containing gas.

[0277] The modified material formed in step (c) can be a nitride of the electroactive material domain. Step (c) can include contacting the surface of the electroactive material domain with ammonia. The nitride layer can be formed by contacting the surface of the electroactive material domain with ammonia at a temperature in the range of 200 - 700 °C, preferably 400 - 700 °C, more preferably 400 - 600 °C. Then, the temperature can be raised to the range of 500 to 1,000 °C if necessary to form a nitride surface (such as a silicon nitride surface of the formula SiNx, where x ≤ 4 / 3). For example, in the case of using ammonia, step (c) can be carried out at a temperature the same as or similar to the temperature used for depositing the electroactive material domain in step (b). Since sub-stoichiometric silicon nitride is conductive, this step also results in the formation of a conductive network, which will enable the electroactive material to charge and discharge more quickly.

[0278] Another type of modified material is an oxynitride layer. Step (c) can include exposing the surface of the electroactive material domain to ammonia (or other nitrogen-containing molecules) and oxygen. In the case where the electroactive material domain contains silicon, the modified material domain can contain silicon oxynitride of the formula SiOxNy, where 0 < x < 2, 0 < y < 4 / 3, and 0 < (2x + 3y) ≤ 4). The silicon oxynitride is preferably amorphous silicon oxynitride.

[0279] As another alternative, an amorphous or nanocrystalline carbide layer can be formed. Step (c) can include contacting the surface of the electroactive material domain with a carbon-containing precursor (such as methane or ethylene) at a temperature in the range of 250 to 700 °C. At a lower temperature, covalent bonds are formed between the surface of the electroactive material and the carbon-containing precursor, and the carbon-containing precursor is converted into a single crystal silicon carbide layer as the temperature increases. In the case where the electroactive material domain contains silicon, the modified material domain can contain silicon carbide of the formula SiCx, where 0 < x ≤ 1. The silicon carbide is preferably amorphous silicon carbide.

[0280] Other suitable passivators include: compounds containing olefinic, acetylenic or carbonyl functional groups, more preferably terminal olefins, terminal acetylenes or aldehyde or ketone groups. These types of suitable passivators are described above.

[0281] Other suitable passivators include compounds containing active hydrogen atoms bonded to oxygen, nitrogen, sulfur or phosphorus. For example, the passivator can be an alcohol, an amine, a thiol or a phosphine. The reaction of the group –XH with the hydride group on the surface of the electroactive material is understood to result in the elimination of H2 and the formation of a direct bond between X and the surface of the electroactive material. These types of suitable passivators are described above.

[0282] The modified material formed in step (c) may optionally comprise pyrolytic carbon material deposited onto the surface of the electroactive material by thermal decomposition of a carbon-containing precursor (i.e. by chemical vapor infiltration (CVI)). The deposition of pyrolytic carbon material in step (c) may be advantageous because it forms a conductive network between the electroactive material domains, which may facilitate electron transport within the composite particle. Thus, step (c) may comprise contacting the intermediate particle from step (b) with a carbon-containing precursor (preferably a hydrocarbon) at a temperature effective to cause deposition of pyrolytic carbon material in the pores of the intermediate particle.

[0283] Suitable hydrocarbons include polycyclic hydrocarbons containing 10 to 25 carbon atoms and optionally 1 to 3 heteroatoms, optionally wherein the polycyclic hydrocarbon is selected from naphthalene, substituted naphthalenes (such as dihydroxynaphthalene), anthracene, tetracene, pentacene, fluorene, dihydroacenaphthene, phenanthrene, fluoranthene, pyrene, Perylene, coronene, fluorenone, anthraquinone, anthrone and their alkyl substituted derivatives. Suitable pyrolytic carbon precursors also include bicyclic monoterpenes, optionally wherein the bicyclic monoterpenes are selected from camphor, borneol, eucalyptol, camphene, careen, sabinene, limonene and pinene. Other suitable pyrolytic carbon precursors include C2-C 10 A hydrocarbon, optionally wherein the hydrocarbon is selected from alkanes, alkenes, alkynes, cycloalkanes, cycloalkenes and aromatic hydrocarbons, such as methane, ethylene, propylene, limonene, styrene, cyclohexane, cyclohexene, α-terpinene and acetylene. Other suitable pyrolytic carbon precursors include phthalocyanine, sucrose, starch, graphene oxide, reduced graphene oxide, pyrene, perhydropyrene, 9,10-triphenylene, tetracene, benzopyrene, perylene, coronene and A preferred carbon precursor is acetylene.

[0284] Temperatures suitable for deposition of the pyrolytic carbon material in step (c) are in the range of 300 to 800°C, or 400 to 800°C. For example, the temperature may be no more than 750°C, or no more than 700°C, or no more than 680°C, or no more than 660°C, or no more than 640°C, or no more than 620°C, or no more than 600°C, or no more than 580°C, or no more than 560°C, or no more than 540°C, or no more than 520°C, or no more than 500°C. The minimum temperature will depend on the type of carbon precursor used. Preferably, the temperature is at least 300°C, or at least 350°C, or at least 400°C, or at least 450°C, or at least 500°C.

[0285] The carbon-containing precursor used in step (c) can be used in pure form or in a mixture diluted with an inert carrier gas such as nitrogen or argon. For example, the carbon-containing precursor can be used in an amount ranging from 0.1% to 100% by volume, or from 0.5% to 20% by volume, or from 1% to 10% by volume, or from 1% to 5% by volume based on the total volume of the precursor and the inert carrier gas. The presence of oxygen should be minimized to prevent undesired oxidation of the deposited electroactive material. Preferably, the oxygen content is less than 0.01% by volume, more preferably less than 0.001% by volume, based on the total volume of the gas.

[0286] In the case of depositing pyrolytic carbon material in step (c), the same compound can act as both a passivator and a pyrolytic carbon precursor. For example, if styrene is selected as the pyrolytic carbon precursor, styrene will also act as a passivator if the intermediate particles from step (b) are not exposed to oxygen before contacting with styrene. In this case, the passivation and deposition of the conductive carbon material in the steps can be carried out simultaneously, for example at a temperature in the range of 300-700°C. Alternatively, the passivation and deposition of the conductive carbon material can be carried out sequentially, using the same material as the passivator and the pyrolytic carbon precursor, but wherein the deposition of the pyrolytic carbon precursor is carried out at a higher temperature than the passivation. For example, the passivation can be carried out at a temperature in the range of 25°C to less than 300°C, and the deposition of the pyrolytic carbon can be carried out at a temperature in the range of 300-700°C. The two steps can be carried out sequentially by increasing the temperature while maintaining contact with the compound that acts as both a passivator and a pyrolytic carbon precursor. At lower temperatures (for example in the range of 25°C to <300°C), the passivation will be the main process. As the temperature increases (eg, to 300-700° C.), deposition of pyrolytic carbon will ensue.

[0287] Alternatively, step (c) may include depositing a layer of a conductive metal or metal alloy as a modifying material onto the surface of the electroactive material domain. The conductive metal layer or metal alloy may be obtained by chemical vapor infiltration (CVI). Examples of suitable conductive metals include silver, gold, copper and titanium.

[0288] The formation of the conductive metal or metal alloy modifying material in step (c) may optionally be carried out after the surface of the electroactive material domain is passivated by one of the above processes. Thus, the modified material formed in step (c) may include both a passivation layer and a conductive metal or metal alloy layer on the surface of the electroactive material domain.

[0289] As another alternative, step (c) may comprise forming a modified material domain comprising an electroactive material comprising a dopant selected from the group consisting of boron, aluminum, gallium, indium, phosphorus, arsenic, antimony and bismuth. The doped electroactive material may be formed by a CVI process, wherein the porous particles are contacted with both a precursor of the electroactive material and the dopant simultaneously. Alternatively, the doped electroactive material may be formed by contacting the deposited electroactive material with the dopant.

[0290] As another alternative, step (c) may include forming a solid electrolyte as the modifying material.

[0291] As another alternative, step (c) may include forming an inert filler as the modifying material.

[0292] Depending on the amount of electroactive material deposited in each step, the method of the present invention can be operated as a multi-pass process, wherein steps (c) and (d) are repeated as many times as necessary to deposit the target amount of electroactive material. For example, steps (c) and (d) can be performed 2 to 15 times, resulting in a total of 3 to 16 electroactive material deposition steps including step (b) and repeated step (d).

[0293] When steps (c) and (d) are repeated, each instance of steps (c) and (d) is independently as described above. For example, each repetition of step (c) may include forming the same or different modified materials. Similarly, the electroactive material deposited in each repetition of step (d) may be the same or different, and may again be the same or different from the electroactive material deposited in step (b). Preferably, the electroactive material deposited in at least one of step (b) and the repeated step (d) is silicon. More preferably, the electroactive material deposited in each of step (b) and the repeated step (d) is silicon.

[0294] When steps (c) and (d) are repeated, the particles used in the repetition of step (c) are the intermediate particles obtained from the previous step (d). Therefore, any reference herein to "particles from step (b)" in the description of step (c) should be interpreted as "particles from the previous step (d)" in the context of any repetition of step (c).

[0295] The method of the present invention optionally further comprises the following steps:

[0296] (e) forming a plurality of modified material domains in the pores and / or on the outer surface of the composite particles from step (d).

[0297] Step (e) is performed immediately after the last electroactive material deposition step (i.e., step (d), or the last repetition of step (d) in the case of repeating steps (c) and (d)). The formation of the modified material domain of step (e) is a process similar to step (c) as described above, except that step (e) is performed after the last electroactive material deposition step (the last step (d)), while step (c) is performed between consecutive electroactive material deposition steps. Any of the modified materials and deposition conditions described above for step (c) also apply to step (e).

[0298] The modifying material domain formed in step (e) may comprise the same or different modifying material as the modifying material domain formed in step (c).

[0299] Optionally, step (e) comprises contacting the composite particles from step (d) with a passivating agent.The preferred passivating agents and passivating conditions as described above in relation to step (c) also apply to the passivation in step (e).

[0300] The modified material domains formed in step (e) may be native oxides of the electroactive material. In this case, it is preferred that the modified material domains formed in step (c) (and any repetitions of step (c)) are not native oxides of the electroactive material.

[0301] Optionally, step (e) comprises depositing a lithium ion permeable material into the pores and / or onto the outer surface of the composite particles from step (d). This provides a further improvement in the performance of the composite particles when used as electroactive materials in lithium ion batteries by reducing the surface area of ​​the composite particles and by sealing the electroactive material domains away from access to the electrolyte.

[0302] The lithium ion permeable material may be deposited immediately after the last electroactive material deposition step (i.e., step (d), or the last step (d) if steps (c) and (d) are repeated more than once. Alternatively, the lithium ion permeable material may be deposited after the first passivation step as discussed above in step (e).

[0303] One suitable lithium ion permeable material is a pyrolytic carbon material. The pyrolytic carbon material can be obtained by chemical vapor infiltration (CVI), ie, by thermally decomposing a volatile carbon-containing gas (eg, ethylene) onto the surface of silicon-containing composite particles.

[0304] One suitable process for depositing the pyrolytic carbon material comprises: combining the composite particles from step (d) with a pyrolytic carbon precursor; and heating the pyrolytic carbon precursor to a temperature effective to cause deposition of the pyrolytic conductive carbon material into the pores and / or on the external surfaces of the composite particles.

[0305] The preferred pyrolytic carbon precursors and pyrolysis conditions described above with respect to step (c) are also applicable to the formation of the pyrolytic carbon material in step (e).

[0306] In the case where the lithium ion permeable material is a pyrolytic carbon material, in step (e), the same compound can act as both a passivating agent and a pyrolytic carbon precursor. Suitable conditions for passivating and forming a pyrolytic carbon material using the same compound as a passivating agent and a pyrolytic carbon precursor in step (e) are the same as those described above for step (c).

[0307] Alternatively, different compounds may be used as the passivating agent and the pyrolytic carbon precursor. For example, the passivating agent may be styrene and the pyrolytic carbon precursor may be a compound such as cyclohexane that is capable of forming a pyrolytic carbon material but is unable to passivate the surface of the electroactive material.

[0308] In a preferred embodiment, the electroactive material deposited in steps (b) and (d) is elemental silicon, and the modified material domain formed in step (c) is a passivation layer comprising an organic moiety covalently bonded to the surface of at least a portion of the elemental silicon domain formed in step (b). Optionally, the method comprises step (e), and the modified material domain formed in step (e) is a silicon oxide domain formed by passivation using an oxygen-containing gas.

[0309] In another preferred embodiment, the electroactive material deposited in steps (b) and (d) is elemental silicon, and the modified material domain formed in step (c) is a pyrolytic carbon domain. Optionally, the method includes step (e), and the modified material domain formed in step (e) is a silicon oxide domain formed by passivation using an oxygen-containing gas.

[0310] In another preferred embodiment, the electroactive material deposited in steps (b) and (d) is elemental silicon, and the modified material domain formed in step (c) is a metal or metal alloy domain. Optionally, the method includes step (e), and the modified material domain formed in step (e) is a silicon oxide domain formed by passivation using an oxygen-containing gas.

[0311] In another preferred embodiment, the electroactive material deposited in steps (b) and (d) is elemental silicon and the modified material domains formed in step (c) are silicon oxide domains formed by passivation using an oxygen-containing gas.

[0312] The process of the invention can be carried out in any reactor capable of bringing solids and gases into contact at high temperature. The porous particles and the composite particles formed can be present in the reactor in the form of a fixed bed of particles or in the form of a moving or stirred bed of particles.

[0313] The product obtained by the process of the invention may have any of the features described herein in relation to the particulate material of the first aspect of the invention.

[0314] In a third aspect of the invention, a composition is provided, comprising the composite particles according to the second aspect of the invention and at least one other component. In particular, a composition is provided, comprising the composite particles according to the second aspect of the invention and at least one other component, the at least one other component being selected from: (i) a binder; (ii) a conductive additive; and (iii) an additional particulate electroactive material. The composition according to the invention can be used as an electrode composition and can therefore be used to form an active layer of an electrode.

[0315] The composition may be a hybrid electrode composition comprising the composite particles and at least one additional particulate electroactive material. Examples of additional particulate electroactive materials include graphite, hard carbon, silicon, tin, germanium, aluminum and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon, and most preferably, the at least one additional particulate electroactive material is graphite.

[0316] In the case of a hybrid electrode composition, the composition may comprise 1 wt % to 95 wt %, or 2 wt % to 90 wt %, or 5 wt % to 85 wt %, or 10 wt % to 80 wt % of particulate material, based on the total dry weight of the composition. The composition preferably comprises 3 wt % to 60 wt %, or 3 wt % to 50 wt %, or 5 wt % to 50 wt %, or 10 wt % to 50 wt %, or 15 wt % to 50 wt % of composite particles, based on the total dry weight of the composition.

[0317] The at least one additional particulate electroactive material is suitably present in an amount of from 20 wt % to 95 wt %, or from 25 wt % to 90 wt %, or from 30 wt % to 75 wt % of the at least one additional particulate electroactive material.

[0318] At least one additional particulate electroactive material D 50 The particle size is preferably in the range of 10 to 50 μm, preferably in the range of 10 to 40 μm, more preferably in the range of 10 to 30 μm, and most preferably in the range of 10 to 25 μm, for example in the range of 15 to 25 μm.

[0319] At least one additional particulate electroactive material D 10 The particle size is preferably at least 5 μm, more preferably at least 6 μm, more preferably at least 7 μm, more preferably at least 8 μm, more preferably at least 9 μm, and still more preferably at least 10 μm.

[0320] At least one additional particulate electroactive material D90 The particle size is preferably at most 100 μm, more preferably at most 80 μm, more preferably at most 60 μm, more preferably at most 50 μm, and most preferably at most 40 μm.

[0321] The at least one additional particulate electroactive material is preferably selected from carbonaceous particles, graphite particles and / or hard carbon particles, wherein the D of the graphite particles and the hard carbon particles is 50 The particle size is in the range of 10 to 50 μm. Still more preferably, the at least one additional particulate electroactive material is selected from graphite particles, wherein the D 50 The particle size ranges from 10 to 50 μm.

[0322] The composition may also be a non-mixed (or "high loading") electrode composition that is substantially free of additional particulate electroactive materials. In this case, the term "substantially free of additional particulate electroactive materials" should be interpreted to mean that the composition contains less than 15 wt%, preferably less than 10 wt%, preferably less than 5 wt%, preferably less than 2 wt%, more preferably less than 1 wt%, more preferably less than 0.5 wt% of any additional electroactive material (i.e., additional materials capable of intercalating and releasing metal ions during charge and discharge of the battery), based on the total dry weight of the composition.

[0323] This type of "high loading" electrode composition preferably comprises at least 50 wt.-%, or at least 60 wt.-%, or at least 70 wt.-%, or at least 80 wt.-%, or at least 90 wt.-% of composite particles according to the invention, based on the total dry weight of the composition.

[0324] The composition may optionally include a binder. The binder serves to adhere the composition to the current collector and maintain the integrity of the composition. Examples of binders that can be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginate and its alkali metal salts, styrene-butadiene rubber (SBR) and polyimide. The composition may include a mixture of multiple binders. Preferably, the binder includes a polymer selected from the following: polyacrylic acid (PAA) and its alkali metal salts, and modified polyacrylic acid (mPAA) and its alkali metal salts, SBR and CMC.

[0325] The binder may suitably be present in an amount of 0.5 to 20 wt%, preferably 1 to 15 wt%, preferably 2 to 10 wt% and most preferably 5 to 10 wt% based on the total dry weight of the composition.

[0326] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking accelerators, coupling agents and / or adhesion promoters.

[0327] The composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials that are included to improve the conductivity between the electroactive components of the composition and the conductivity between the electroactive components of the composition and the current collector. Conductive additives may be selected from carbon black, carbon fiber, carbon nanotubes, graphene, acetylene black, ketjen black, metal fibers, metal powders, and conductive metal oxides. Preferred conductive additives include carbon black and carbon nanotubes.

[0328] One or more conductive additives may suitably be present in a total amount of 0.5 to 20 wt%, preferably 1 to 15 wt%, preferably 2 to 10 wt% and most preferably 5 to 10 wt%, based on the total dry weight of the composition.

[0329] The present invention provides an electrode comprising a particulate material according to the present invention in electrical contact with a current collector.The particulate material used to prepare the electrode may be in the form of a composition of the present invention.

[0330] As used herein, the term current collector refers to any conductive substrate capable of carrying an electric current to the electroactive particles in the composition and carrying an electric current out of the electroactive particles in the composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium and sintered carbon. Copper is a preferred material. The current collector is typically in the form of a foil or mesh having a thickness of 3 to 500 μm. The granular material of the present invention can be applied to one or both surfaces of the current collector to a thickness preferably in the range of 10 μm to 1 mm, for example 20 to 500 μm or 50 to 200 μm.

[0331] The electrode of the present invention can be prepared in the following manner: the granular material of the present invention is combined with a solvent and one or more optional viscosity regulating additives to form a slurry. The slurry is then cast onto the surface of the current collector, and the solvent is removed to form an electrode layer on the surface of the current collector. Additional steps may be performed as appropriate, such as heat treatment for curing any binder and / or calendering of the electrode layer. The thickness of the electrode layer is suitably in the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, preferably 20 μm to 50 μm.

[0332] Alternatively, the slurry can be formed into a self-supporting film or mat comprising the particulate material of the present invention, for example by casting the slurry onto a suitable casting template, removing the solvent and then removing the casting template. The resulting film or mat is in the form of a cohesive, self-supporting object, which can then be combined with a current collector by known methods.

[0333] The electrode of the present invention can be used as the anode of a metal ion battery. Therefore, the present invention provides a rechargeable metal ion battery, which comprises: an anode, the anode comprising an electrode according to the present invention as described above; a cathode, the cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; and an electrolyte between the anode and the cathode.

[0334] The metal ion is preferably a lithium ion. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery, and the cathode active material is capable of releasing and accepting lithium ions.

[0335] The cathode active material is preferably a composite material based on metal oxides. Examples of suitable cathode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2、LiCo 0.7 Ni 0.3 O2、LiCo 0.8 Ni 0.2 O2、LiCo 0.82 Ni 0.18 O2、LiCo 0.8 Ni 0.15 Al 0.05 O2、LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The cathode current collector generally has a thickness of 3 to 500 μm. Examples of materials that can be used as the cathode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.

[0336] Electrolyte is suitably a non-aqueous electrolyte containing a metal salt (e.g., a lithium salt), and may include, but is not limited to, a non-aqueous electrolyte, a solid electrolyte, and an inorganic solid electrolyte. Examples of usable non-aqueous electrolyte solutions include aprotic organic solvents, such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, sulfolane, methyl sulfolane, and 1,3-dimethyl-2-imidazolidinone.

[0337] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups.

[0338] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts (such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4).

[0339] The lithium salt is suitably soluble in the selected solvent or solvent mixture. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li and CF3SO3Li.

[0340] In the case where the electrolyte is a non-aqueous organic solution, the metal ion battery preferably has a separator between the anode and the cathode. The separator is typically formed of an insulating material having high ion permeability and high mechanical strength. The separator typically has a pore size of 0.01 to 100 μm and a thickness of 5 to 300 μm. Examples of suitable electrode separators include microporous polyethylene films.

[0341] The separator may be replaced by a polymer electrolyte material, and in such a case, the polymer electrolyte material is present in both the composite anode layer and the composite cathode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte.

Claims

1. A granular material consisting of a plurality of composite particles, wherein the composite particles comprise: (a) a porous particle framework comprising micropores and / or mesopores, wherein the total pore volume of the micropores and mesopores measured by gas adsorption is between 0.4 and 2.2 cm 3 / g range; (b) a plurality of electroactive material domains and a plurality of modifying material domains disposed within the interior pore volume of the porous particle framework, wherein at least a portion of the modifying material domains are located between adjacent electroactive material domains.

2. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.45 and 2.2 cm 3 / g range.

3. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.5 and 2 cm 3 / g range.

4. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.55 and 2 cm 3 / g range.

5. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.6 and 1.8 cm 3 / g range.

6. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.65 and 1.8 cm 3 / g range.

7. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.7 and 1.6 cm 3 / g range.

8. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.7 and 1.5 cm 3 / g range.

9. The particulate material of claim 1, wherein the total pore volume of micropores and mesopores in the porous particle skeleton is between 0.7 and 1.4 cm 3 / g range.

10. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 30nm.

11. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 25 nm.

12. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 20 nm.

13. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 15 nm.

14. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 12 nm.

15. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 10 nm.

16. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 8 nm.

17. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 6 nm.

18. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 5 nm.

19. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 4 nm.

20. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 3 nm.

21. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 2.5 nm.

22. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 2 nm.

23. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 50 The pore size does not exceed 1.5 nm.

24. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 25 nm.

25. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 20 nm.

26. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 15 nm.

27. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 12 nm.

28. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 10 nm.

29. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 8 nm.

30. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 6 nm.

31. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 5 nm.

32. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 4 nm.

33. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 3 nm.

34. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 2.5 nm.

35. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 2 nm.

36. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 30 The pore size does not exceed 1 nm.

37. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​100 m 2 / g to 4,000 m 2 / g range.

38. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​750 m 2 / g to 3,500 m 2 / g range.

39. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​1,000 m 2 / g to 3,250 m 2 / g range.

40. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​1,000 m 2 / g to 3,000 m 2 / g range.

41. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​1,000 m 2 / g to 2,500 m 2 / g range.

42. The particulate material of claim 1, wherein the porous particle skeleton has a BET surface area of ​​1,000 m 2 / g to 2,000 m 2 / g range.

43. The particulate material of claim 1, wherein the porous particle skeleton is an electrically conductive porous particle skeleton.

44. The particulate material of claim 43, wherein the conductive porous particle framework is a conductive porous carbon particle framework.

45. The particulate material of claim 44, wherein the conductive porous carbon particle framework comprises at least 80% carbon by weight.

46. ​​The particulate material of claim 44, wherein the conductive porous carbon particle framework comprises at least 85% carbon by weight.

47. The particulate material of claim 44, wherein the conductive porous carbon particle framework comprises at least 90% carbon by weight.

48. The particulate material of claim 44, wherein the conductive porous carbon particle framework comprises at least 95% carbon by weight.

49. The particulate material of claim 1, wherein the porous particle skeleton has a volume ratio of micropores to mesopores of from 90:10 to 30:

70.

50. The particulate material of claim 1, wherein the porous particle framework has a volume ratio of micropores to mesopores of from 85:15 to 40:

60.

51. The particulate material of claim 1, wherein the porous particle skeleton has a volume ratio of micropores to mesopores of from 80:20 to 50:

50.

52. The particulate material of claim 1, wherein the porous particle skeleton has a volume ratio of micropores to mesopores of from 70:30 to 55:

45.

53. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 10 nm.

54. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 9 nm.

55. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 8 nm.

56. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 7 nm.

57. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 6 nm.

58. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 5 nm.

59. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 4 nm.

60. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 3 nm.

61. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 2.5 nm.

62. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 2 nm.

63. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 1.5 nm.

64. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 10 The pore size does not exceed 1 nm.

65. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 35 nm.

66. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 30 nm.

67. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 25 nm.

68. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 20 nm.

69. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 15 nm.

70. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 12 nm.

71. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 10 nm.

72. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 8 nm.

73. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 6 nm.

74. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 5 nm.

75. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 4 nm.

76. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 3 nm.

77. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 2.5 nm.

78. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore size does not exceed 2 nm.

79. The particulate material of claim 1, wherein each of the electroactive material domains comprises an electroactive material independently selected from the group consisting of silicon, tin, germanium, aluminum, and mixtures and alloys thereof.

80. The particulate material of claim 1, wherein at least a portion of the electroactive material domains comprise silicon.

81. The particulate material of claim 1, wherein at least a portion of the electroactive material domains are composed of silicon.

82. The particulate material of claim 1, wherein all of the electroactive material domains comprise silicon.

83. The particulate material of claim 1, wherein all of the electroactive material domains are composed of silicon.

84. The particulate material of claim 1, wherein the modifying material comprises one or more of carbon, nitrogen, and oxygen.

85. The particulate material of claim 84, wherein the modifying material is an oxide, nitride, oxynitride, or carbide passivation layer formed on the surface of at least a portion of the electroactive material domains.

86. The particulate material of claim 85, wherein the modifying material is selected from SiO x Oxide, where 0 <x≤2。 87. The particulate material of claim 85, wherein the modifying material is selected from SiN x of nitride, where 0 <x≤4 / 3。 88. The particulate material of claim 85, wherein the modifying material is selected from SiC x of carbides, of which 0 <x≤1。 89. The particulate material of claim 84, wherein the modifying material is a passivating layer comprising a carbon-containing organic moiety covalently bonded to a surface of at least a portion of the electroactive material domains.

90. The particulate material of claim 1, wherein the modifying material comprises a C-terminal domain covalently bonded to the surface of at least a portion of the electroactive material domains. 2-22 Hydrocarbon.

91. The particulate material of claim 1, wherein the modifying material comprises a C-terminal domain covalently bonded to the surface of at least a portion of the electroactive material domain. 2-22 Alkyl, C 2-22 Alkenyl, C 2-22 Alkynyl, C 3-22 Cycloalkyl, C 3-22 Cycloalkenyl, C 3-22 Cycloalkynyl or C 6-22 Aralkyl.

92. The particulate material of claim 1, wherein the modifying material is selected from the group consisting of: ; ; ; ; ; ; ; ; ; ; ; ; ;or .

93. The particulate material of claim 84, wherein the modified material comprises a pyrolytic carbon material.

94. The particulate material of claim 1, wherein the modifying material comprises a conductive metal or metal alloy.

95. The particulate material of claim 1, wherein the modifying material comprises an electroactive material comprising a dopant selected from boron and phosphorus.

96. The particulate material of claim 1, further comprising an external modifying material domain located between the outermost electroactive material domain and the exterior of the composite particle, optionally wherein the modifying material is selected from the modifying materials described in any one of claims 84 to 89 and 93 to 95.

97. The particulate material of claim 1, comprising 5% to 85% by weight of the electroactive material, based on the total mass of the composite particle.

98. The particulate material of claim 1, comprising 10% to 85% by weight of the electroactive material, based on the total mass of the composite particle.

99. The particulate material of claim 1, comprising 15% to 85% by weight of the electroactive material, based on the total mass of the composite particle.

100. The particulate material of claim 1, comprising 20% ​​to 80% by weight of the electroactive material, based on the total mass of the composite particle.

101. The particulate material of claim 1, comprising 25% to 80% by weight of the electroactive material, based on the total mass of the composite particle.

102. The particulate material of claim 1, comprising 30% to 75% by weight of the electroactive material, based on the total mass of the composite particle.

103. The particulate material of claim 1, comprising 35% to 75% by weight of the electroactive material, based on the total mass of the composite particle.

104. The particulate material of claim 1, comprising 40% to 70% by weight of the electroactive material, based on the total mass of the composite particle.

105. The particulate material of claim 1, comprising 45% to 65% by weight of the electroactive material, based on the total mass of the composite particle.

106. The particulate material of claim 1, wherein the composite particle comprises 40% to 70% by weight of the electroactive material, based on the total mass of the composite particle.

107. The particulate material of claim 1, wherein the composite particle comprises 45% to 70% by weight of the electroactive material, based on the total mass of the composite particle.

108. The particulate material of claim 1, wherein the composite particle comprises 48% to 70% by weight of the electroactive material, based on the total mass of the composite particle.

109. The particulate material of claim 1, wherein the composite particle comprises 50% to 70% by weight of the electroactive material, based on the total mass of the composite particle.

110. The particulate material of claim 1, wherein the composite particle comprises 40% to 65% by weight of the electroactive material, based on the total mass of the composite particle.

111. The particulate material of claim 1, wherein the composite particle comprises 45% to 65% by weight of the electroactive material, based on the total mass of the composite particle.

112. The particulate material of claim 1, wherein the composite particle comprises 48% to 65% by weight of the electroactive material, based on the total mass of the composite particle.

113. The particulate material of claim 1, wherein the composite particle comprises 50% to 65% by weight of the electroactive material, based on the total mass of the composite particle.

114. The particulate material of claim 1, wherein the composite particle comprises 40% to 60% by weight of the electroactive material, based on the total mass of the composite particle.

115. The particulate material of claim 1, wherein the composite particle comprises 45% to 60% by weight of the electroactive material, based on the total mass of the composite particle.

116. The particulate material of claim 1, wherein the composite particle comprises 48% to 60% by weight of the electroactive material, based on the total mass of the composite particle.

117. The particulate material of claim 1, wherein the composite particle comprises 50% to 60% by weight of the electroactive material, based on the total mass of the composite particle.

118. The particulate material of claim 1, wherein the composite particles comprise 10 wt% to 85 wt% silicon, based on the total mass of the composite particles.

119. The particulate material of claim 1, wherein the composite particles comprise 15 wt% to 85 wt% silicon, based on the total mass of the composite particles.

120. The particulate material of claim 1, wherein the composite particles comprise 20 wt% to 80 wt% silicon, based on the total mass of the composite particles.

121. The particulate material of claim 1, wherein the composite particles comprise 25 wt% to 80 wt% silicon, based on the total mass of the composite particles.

122. The particulate material of claim 1, wherein the composite particles comprise 30 wt% to 75 wt% silicon, based on the total mass of the composite particles.

123. The particulate material of claim 1, wherein the composite particles comprise 35 wt% to 75 wt% silicon, based on the total mass of the composite particles.

124. The particulate material of claim 1, wherein the composite particles comprise 40 wt% to 70 wt% silicon, based on the total mass of the composite particles.

125. The particulate material of claim 1, wherein the composite particles comprise 45 wt% to 65 wt% silicon, based on the total mass of the composite particles.

126. The particulate material of claim 1, wherein the composite particles comprise 40 wt% to 70 wt% silicon, based on the total mass of the composite particles.

127. The particulate material of claim 1, wherein the composite particles comprise 45 wt% to 70 wt% silicon, based on the total mass of the composite particles.

128. The particulate material of claim 1, wherein the composite particles comprise 48 wt% to 70 wt% silicon, based on the total mass of the composite particles.

129. The particulate material of claim 1, wherein the composite particles comprise 50 wt% to 70 wt% silicon, based on the total mass of the composite particles.

130. The particulate material of claim 1, wherein the composite particles comprise 40 wt% to 65 wt% silicon, based on the total mass of the composite particles.

131. The particulate material of claim 1, wherein the composite particles comprise 45 wt% to 65 wt% silicon, based on the total mass of the composite particles.

132. The particulate material of claim 1, wherein the composite particles comprise 48 wt% to 65 wt% silicon, based on the total mass of the composite particles.

133. The particulate material of claim 1, wherein the composite particles comprise 50 wt% to 65 wt% silicon, based on the total mass of the composite particles.

134. The particulate material of claim 1, wherein the composite particles comprise 40 wt% to 60 wt% silicon, based on the total mass of the composite particles.

135. The particulate material of claim 1, wherein the composite particles comprise 45 wt% to 60 wt% silicon, based on the total mass of the composite particles.

136. The particulate material of claim 1, wherein the composite particles comprise 48 wt% to 60 wt% silicon, based on the total mass of the composite particles.

137. The particulate material of claim 1, wherein the composite particles comprise 50 wt% to 60 wt% silicon, based on the total mass of the composite particles.

138. The particulate material of claim 1, wherein the amount of electroactive material occupies at least 25% and at most 90% of the internal pore volume of the porous particle skeleton.

139. The particulate material of claim 1, wherein at least 85 weight percent of the mass of electroactive material in the composite particles is located within the internal pore volume of the porous particle skeleton.

140. The particulate material of claim 1, wherein at least 90 weight percent of the mass of electroactive material in the composite particles is located within the internal pore volume of the porous particle skeleton.

141. The particulate material of claim 1, wherein at least 95 weight percent of the mass of electroactive material in the composite particles is located within the internal pore volume of the porous particle skeleton.

142. The particulate material of claim 1, wherein at least 98 weight percent of the mass of electroactive material in the composite particles is located within the internal pore volume of the porous particle skeleton.

143. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 0.5 to 30 µm.

144. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 1 to 25 µm.

145. The granular material of claim 1, wherein the D of the composite particles 50 Particle sizes range from 1 to 20 µm.

146. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 1 to 18 µm.

147. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 1 to 16 µm.

148. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 2 to 16 µm.

149. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 2 to 14 µm.

150. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 2 to 12 µm.

151. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 2 to 10 µm.

152. The granular material of claim 1, wherein the D of the composite particles 50 The particle size ranges from 2 to 8 µm.

153. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​0.1 to 100 m 2 / g range.

154. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​0.1 to 80 m 2 / g range.

155. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​0.5 to 60 m 2 / g range.

156. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​0.5 to 40 m 2 / g range.

157. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​1 to 30 m 2 / g range.

158. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​1 to 25 m 2 / g range.

159. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​2 to 20 m 2 / g range.

160. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 15 wt % based on the total mass of the composite particles.

161. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 10 wt % based on the total mass of the composite particles.

162. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 5 wt % based on the total mass of the composite particles.

163. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 4 wt % based on the total mass of the composite particles.

164. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 3 wt % based on the total mass of the composite particles.

165. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 2 wt % based on the total mass of the composite particles.

166. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 1 wt % based on the total mass of the composite particles.

167. The particulate material of claim 1, wherein the composite particles comprise a total oxygen content of less than 0.5 wt % based on the total mass of the composite particles.

168. The particulate material of claim 1, wherein the composite particles comprise a total chlorine content of less than 100 ppm based on the total mass of the composite particles.

169. The particulate material of claim 1, wherein the composite particles comprise a total chlorine content of less than 90 ppm based on the total mass of the composite particles.

170. The particulate material of claim 1, wherein the composite particles comprise a total chlorine content of less than 80 ppm based on the total mass of the composite particles.

171. The particulate material of claim 1, wherein the composite particles comprise a total chlorine content of less than 70 ppm based on the total mass of the composite particles.

172. The particulate material of claim 1, wherein the composite particles comprise a combined content of transition metals and alkali metals of less than 0.5 wt. %, based on the total weight of the composite particles.

173. The particulate material of claim 1, wherein the composite particles comprise 0.0001 wt% to 0.5 wt% zirconium, based on the total weight of the composite particles.

174. The granular material of claim 1, wherein the D of the composite particles 10 The particle size is at least 0.5 µm.

175. The granular material of claim 1, wherein the D of the composite particles 10 The particle size is at least 0.8 µm.

176. The granular material of claim 1, wherein the D of the composite particles 10 The particle size is at least 1 µm.

177. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is not more than 50 µm.

178. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is not more than 40 µm.

179. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is not more than 30 µm.

180. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is no more than 25 µm.

181. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is not more than 20 µm.

182. The granular material of claim 1, wherein the D of the composite particles 90 The particle size is not more than 15 µm.

183. The particulate material of claim 1, wherein the composite particles have a particle size distribution span (D ) of 5 or less. 90 -D 10 ) / D 50 ).

184. The particulate material of claim 1, wherein the composite particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

185. The particulate material of claim 1, wherein the composite particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

186. The particulate material of claim 1, wherein the composite particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

187. The particulate material of claim 1, wherein the composite particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

188. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.35 cm 3 / g.

189. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.25 cm 3 / g.

190. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.15 cm 3 / g.

191. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.1 cm 3 / g.

192. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.05 cm 3 / g.

193. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.03 cm 3 / g.

194. The particulate material of claim 1, wherein the total volume of the micropores and mesopores of the composite particles is no more than 0.02 cm 3 / g.

195. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 10 weight percent of the silicon is bulk phase silicon as determined by TGA.

196. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 8 weight percent of the silicon is macrophase silicon as determined by TGA.

197. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 6 weight percent of the silicon is macrophase silicon as determined by TGA.

198. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 5 weight percent of the silicon is macrophase silicon as determined by TGA.

199. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 4 weight percent of the silicon is macrophase silicon as determined by TGA.

200. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 3 weight percent of the silicon is bulk phase silicon as determined by TGA.

201. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 2 weight percent of the silicon is bulk phase silicon as determined by TGA.

202. The particulate material of claim 1 wherein the electroactive material is silicon and no more than 1.5 weight percent of the silicon is macrophase silicon as determined by TGA.

203. The particulate material of claim 1, wherein the electroactive material is silicon and at least 22 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

204. The particulate material of claim 1, wherein the electroactive material is silicon and at least 25 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

205. The particulate material of claim 1, wherein the electroactive material is silicon and at least 30 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

206. The particulate material of claim 1, wherein the electroactive material is silicon and at least 35 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

207. The particulate material of claim 1, wherein the electroactive material is silicon and at least 40 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

208. The particulate material of claim 1, wherein the electroactive material is silicon and at least 45 weight percent of the silicon is surface silicon as determined by thermogravimetric analysis (TGA).

209. The particulate material of claim 1, wherein the PD of the porous particle skeleton is 90 The pore diameters range from 2.5 to 20 nm.

210. A method for preparing composite particles, the method comprising the steps of: (a) providing a plurality of porous particles including micropores and / or mesopores, wherein the total pore volume of the micropores and mesopores measured by gas adsorption is in the range of 0.4 to 2.2 cm 3 / g range; (b) contacting the porous particle with a precursor of an electroactive material at a temperature effective to cause deposition of a plurality of electroactive material domains in the pores of the porous particle; (c) forming a plurality of modified material domains in the pores of the porous particle and adjacent to the electroactive material domains deposited in step (b); (d) contacting the particles from step (c) with a precursor of an electroactive material at a temperature effective to cause deposition of additional electroactive material domains in the pores of the porous particles and adjacent to the modified material domains formed in step (c).

211. The method of claim 210, wherein the porous particle has any one of the features described in claims 2 to 8 regarding the porous particle skeleton.

212. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 0.5 to 30 µm.

213. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 1 to 25 µm.

214. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 1 to 20 µm.

215. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 25 µm.

216. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 20 µm.

217. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 18 µm.

218. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 15 µm.

219. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 12 µm.

220. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2.5 to 15 µm.

221. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2.5 to 12 µm.

222. The method of claim 210, wherein the porous particles have a D 50 The particle size ranges from 2 to 10 µm.

223. The method of claim 210, wherein the electroactive materials deposited in steps (b) and (d) are independently selected from silicon, tin, germanium, aluminum, and mixtures and alloys thereof.

224. The method of claim 210, wherein the electroactive material deposited in each of steps (b) and (d) is silicon.

225. The method of claim 210, wherein the precursor of the electroactive material in each of steps (b) and (d) is independently selected from monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8), tetrasilane (Si4H 10 ), methylsilane, dimethylsilane and chlorosilane.

226. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 300 to 800°C.

227. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 350 to 800°C.

228. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 380 to 700°C.

229. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 380 to 650 °C.

230. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 380 to 600°C.

231. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 380 to 550°C.

232. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 380 to 500°C.

233. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 400 to 450°C.

234. The method of claim 210, wherein steps (b) and (d) are independently performed at a temperature in the range of 450 to 500°C.

235. The method of claim 210, wherein step (b) and / or step (d) further comprises separating by-products from the particles.

236. The method of claim 210, wherein step (c) comprises contacting the intermediate particles from step (b) with a passivating agent.

237. The method of claim 236, wherein the passivating agent is selected from the group consisting of: (i) an oxygen-containing gas; (ii) ammonia; (iii) a gas comprising ammonia and oxygen; and (iv) phosphine.

238. The method of claim 236, wherein the passivating agent is selected from: (i)R 1 -CH=CH-R 1 ; (ii) R 1 -C≡CR 1 4 (iii)O=CR 1 R 1 ; (iv)HX-R 2 ,and (v)HX-C(O)-R 1 , Where X represents O, S, NR 1 or PR 1 ;and Each R 1 independently represent H or an unsubstituted or substituted aliphatic or aromatic hydrocarbon group having 1 to 20 carbon atoms, or wherein two R 1 The group forms an unsubstituted or substituted ring structure containing 3 to 8 carbon atoms in the ring; Where R 2 represents an unsubstituted or substituted aliphatic or aromatic hydrocarbon group having 1 to 20 carbon atoms, or wherein R 1 and R 2 Together they form an unsubstituted or substituted ring structure comprising 3 to 8 carbon atoms in the ring.

239. The method of claim 236, wherein the passivating agent is selected from the group consisting of ethylene, propylene, 1-butene, butadiene, 1-pentene, 1,4-pentadiene, 1-hexene, 1-octene, styrene, divinylbenzene, acetylene, phenylacetylene, norbornene, norbornadiene, and bicyclo[2.2.2]oct-2-ene.

240. The method of claim 210, wherein step (c) comprises contacting the intermediate particles from step (b) with a carbon-containing precursor at a temperature effective to cause deposition of pyrolytic carbon material in the pores of the intermediate particles.

241. The method of claim 210, wherein steps (c) and (d) are repeated more than once.

242. The method of claim 210, further comprising the steps of: (e) forming a plurality of modified material domains in the pores and / or on the outer surface of the composite particles from step (d).

243. A method according to claim 242, wherein step (e) comprises contacting the surface of the composite particles from the last step (d) with a passivating agent, optionally wherein the passivating agent is as defined in claim 237 or 238.

244. The method of claim 242, wherein step (e) comprises: combining the composite particles from step (d) with a pyrolytic carbon precursor; and heating the pyrolytic carbon precursor to a temperature effective to cause deposition of pyrolytic conductive carbon material into the pores and / or on the outer surfaces of the composite particles.

245. The method of claim 210, wherein the porous particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

246. The method of claim 210, wherein the porous particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

247. The method of claim 210, wherein the porous particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

248. The method of claim 210, wherein the porous particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

249. The method of claim 210, wherein the porous particles have a particle size distribution span (D 90 -D 10 ) / D 50 ).

250. The method of claim 210, wherein the PD of the porous particles 90 The pore diameters range from 2.5 to 20 nm.

251. A composition comprising the particulate material of claim 1 and at least one other component.

252. An electrode comprising the particulate material of claim 1 or the composition of claim 251.

253. A rechargeable metal ion battery, comprising the electrode of claim 252.

Citation Information

Patent Citations

  • A method of fabricating fibres composed of silicon or a silicon-based material and their use in lithium rechargeable batteries

    WO2007083155A1

  • Electroactive materials for metal-ion batteries

    WO2020095067A1

  • Electroactive materials for metal-ion batteries

    WO2020128495A1

  • Decomposition of silicon-containing precursors on porous scaffold materials

    US20200020935A1